Rare and common variants in ERAP1 and ERAP2 selected for in response to Yersinia pestis infection contribute to autoimmune disease including inflammatory bowel disease - Lynn K. Win; Guo Cheng; James J. Ashton; Alex Z. Kadhim; Zachary Green; R. Mark Beattie; Sarah Ennis (Mammalian Genome, 2026)
Endoplasmic reticulum aminopeptidases (ERAP) facilitate antigen presentation. Variation in ERAP1 and ERAP2 genes underwent selection during the Black Death and impact autoimmune disease susceptibility. We assess the burden of functionally impactful variants present in ERAP1 and ERAP2 in 2 cohorts of patients diagnosed with inflammatory bowel disease (IBD; Crohn’s disease (CD) or ulcerative colitis (UC)). We analysed the Southampton Genetics of IBD cohort comprising patients diagnosed with IBD, with exome and clinical data on autoimmune comorbidities (n CD = 661, n UC = 330); and a subset of UK Biobank IBD patients and selected controls (n CD = 891, n UC = 1409, n control = 60,075). Common single variants (minor-allele-frequency > 0.05) underwent Fisher’s exact test with permutations (n = 1000), comparing UC versus CD patients in the Southampton cohort. A gene-burden based test of functionally impactful variants (GenePy) was used to examine rare and common variants in both cohorts. Predicted haplotypes were assessed in each cohort and compared with known haplotypes of ERAP1 and ERAP2 . In the Southampton cohort, variant-level analysis identified 6 common variants that were nominally significant when testing between UC versus CD ( p < 0.05; empirical permuted p-value). Gene-level analysis using Mann–Whitney-U identified an altered burden of functionally impactful variants for ERAP1 in UC versus CD patients ( p = 0.0073), but not for ERAP2 . Patients with an isolated diagnosis of UC ( p = 0.037,θ = 0.457) vs patients with a concurrent diagnosis of UC and any autoimmune diagnoses had an altered burden of functionally impactful variants in ERAP2 . For the UK Biobank cohort, participants diagnosed with UC versus controls had a significantly altered burden of functionally impactful variants in ERAP1 ( p = 0.0004) and ERAP2 ( p = 0.0006). Both variant and gene-level analysis indicate a role for ERAP1 and ERAP2 in predisposing individuals to developing UC or UC with concurrent autoimmune diagnosis.

Overlooked properties difference of biogenic sulfur resulting in distinct performance in serving as an electron donor for microbial denitrification - N. Zhang; G. Yi; R. Ren; G. Zhang; D. Ren; X. Ba; H. Xu; H.-Y. Cheng (Water Research, 2026)

Characterizing effects of tree mortality from wildfire and bark beetles using satellite observations of solar-induced chlorophyll fluorescence - Lewis Kunik; David R. Bowling; Brett Raczka; Jeffrey A. Hicke; Christian Frankenberg; Rui Cheng; Michèle R. Slaton; John C. Lin (Remote Sensing of Environment, 2026)

Millennial-to multi-centennial-scale Asian summer monsoon variability during Termination I: Evidence from stalagmite δ18O in Wanxiang Cave, northwestern China - Hongyu Shi; Pingzhong Zhang; Xianfeng Wang; Shaoneng He; Shufang Yuan; Ruitao Deng; Wei Jia; Shuyu Xue; Hai Cheng; R. Lawrence Edwards (Quaternary Science Reviews, 2026)

Perfluorooctanoic acid exposure disrupts gut microbiota and aggravates experimental colitis - Dekun Cheng; Guangyi Shen; Jathya C. Pathiranage; Yin Zhao; Junkai Xie; Qianyue Wang; Christina R. Ferreira; Qingfei Zheng; Chongli Yuan; Weicang Wang (Environmental Pollution, 2026)

Social bonds between nonkin are common, but less stable, in a mixed-related society - Zhuli Cheng; André S. Pereira; Susan Anton; Lauren Brent; James Higham; Melween Martinez; Amanda Melin; Michael Montague; Michael Platt; Jerome Sallet; Noah Snyder-Mackler; Josué E. Negron-Del Valle; et al. (Animal Behaviour, 2026)

Detrital U–Pb and Lu–Hf zircon signatures from the Shackleton Range, East Antarctica: Implications for supercontinent assembly in Nuna, Rodinia, and Gondwana - Joachim Jacobs; Andreas Läufer; Cheng-Cheng Wang; Yngve Fossheim; Guillaume Jacques; Leif-Erik R. Pedersen (Precambrian Research, 2026)

Reconstructing historical extreme precipitation from an aragonite-calcite stalagmite using trace-element ratios - Jiayu Lu; Haiwei Zhang; Hanying Li; Xinnan Zhao; Rui Zhang; Lijuan Sha; Jian Wang; Xiyu Dong; R. Lawrence Edwards; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Association between ambient air pollution and colorectal cancer risk: The Multiethnic Cohort Study - Ugonna Ihenacho; Chiuchen Tseng; Jun Wu; Scott Fruin; Timothy V. Larson; Salma Shariff-Marco; Loïc Le Marchand; Daniel O. Stram; Brian Z. Huang; Lynne R. Wilkens; Christopher A. Haiman; Beate Ritz; et al. (Environmental Research, 2026)

Effects of Surface Freshwater Flows on Vertical Exchange with Porewater Salinity and Ammonium Availability in a Louisiana Salt Marsh Soil; A laboratory study - Jacob Z. Cheng; Robert Feder; John R. White (Estuarine, Coastal and Shelf Science, 2026)

Associations of neighborhood racial and ethnic, economical, and educational segregation with breast cancer risk: The Multiethnic ohort Study - Ugonna Ihenacho; Jenna Khan-Gates; Katherine Lin; Janine V. Abe; Pushkar P. Inamdar; Juan Yang; Yuqing Li; Meera Sangaramoorthy; Christopher A. Haiman; Loïc Le Marchand; Lynne R. Wilkens; Scarlett Lin Gomez; et al. (Cancer Causes & Control, 2026)
Purpose Residential segregation is recognized as an upstream driver of poor health, yet few studies have evaluated its impact on breast cancer incidence at a local level. We examined associations of neighborhood residential segregation with breast cancer (BC) incidence in the Multiethnic Cohort Study (MEC). Methods Measures of Index of Concentration at the Extremes were developed to assess residential segregation by income, education, race and ethnicity, and racialized income. A prospective study (1993–1996 through December 2019) was conducted to examine associations of these measures and breast cancer incidence for 101,785 African American, Japanese American, Latina, Native Hawaiian, and White female participants in the MEC, aged 45–75 years at baseline and residing in California and Hawai‘i. Multivariable Cox regression was conducted to evaluate the associations of several residential segregation measures with breast cancer incidence (cases = 7,381) adjusting for demographic, lifestyle, and reproductive factors. Results In California, BC risk was higher for females residing in neighborhoods with the highest compared to lowest concentration of privilege by income segregation (quintile 5 [Q5] vs. Q1: hazard ratio [HR] 1.12, 95% confidence interval [CI] 1.00–1.25, P trend = 0.001) and education segregation (Q5 vs. Q1: HR 1.15, 95% CI 1.01–1.31; P trend = 0.01). For Latina females, risks increased with increasing privilege for measures of income, education, race and ethnicity, and racialized income residential segregation ( P trends < 0.05). No associations were observed in Hawai‘i. Conclusion In California, residential economic privilege was independently associated with increased BC risk. Future studies should examine neighborhood- and individual-level pathways placing females residing in privileged areas at greater risk.

Glucose but not fructose ingestion improves endurance cycling performance despite similar neuromuscular fatigue at exhaustion - Andrew J. Richards; Parsa Jamal-Zadeh; Ava R. Silva; Rohin Malekzadeh; Lauren V. Turner; Robert Laham; Michael C. Riddell; Devin B. Phillips; Arthur J. Cheng (European Journal of Applied Physiology, 2026)

Antidepressant effects of Gardeniae Fructus on chronic unpredictable mild stress model mice: involvement of DNMT3B-mediated epigenetic regulation of GR in the prefrontal cortex - Lu-Lu Zhang; Xiao-Wei Wang; Yi-Dan Cheng; Ya Liu; Hesham R. El-Seedi; Peng-Cheng Sun; Wen-bin He; Jian-Jun Zhang; Zhi-Guang Zhai (Journal of Natural Medicines, 2026)

Retraction notice to “Facile synthesis of CaFe2O4 for visible light driven treatment of polluting palm oil mill effluent: Photokinetic and scavenging study” [Sci. Total Environ. 661 (2019) 522–530] - Ashwin Charles; Maksudur R. Khan; Kim Hoong Ng; Ta Yeong Wu; Jun Wei Lim; Suwimol Wongsakulphasatch; Thongthai Witoon; Chin Kui Cheng (Science of The Total Environment, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Environmental ocurrence of Salmonella Dublin in Midwest U.S. dairy-beef operations: Associations with biosecurity and farm management - Alejandra Arevalo-Mayorga; Samantha R. Locke; Ting-Yu Cheng; Jarred Kopkey; Andreia Arruda; Greg Habing (Preventive Veterinary Medicine, 2026)

Surrogate model-assisted NSGA-II optimisation of a dynamic power cable configuration for a floating offshore wind turbine - A. Holcombe; M. Hann; S. Brown; J. Holcombe; R. Nicholls-Lee; S. Cheng; R. Rawlinson-Smith (Ocean Engineering, 2026)

Metabolic pathway for aerobic methane production in Burkholderia sp. HQL 1813 - Zeqin Liu; Zhengzheng Zhao; Zilong Cheng; Shiqi Xu; Xiaoyu Zhang; Spencer R. Moller; Minmin Cai; Ruth Elaine Blake; Chan Yu (Chemical Engineering Journal, 2026)

Marine protected areas do not affect benthic invertebrate communities in North Sulawesi, Indonesia - Ana Setyastuti; Hendrik A. W. Cappenberg; Eghbert Elvan Ampou; Udhi Eko Hernawan; Frensly Demianus Hukom; Jemmy Souhoka; Akira W. R. Masengi; Ixchel Feibie Mandagi; Kawilarang W. A. Masengi; Min Hui; Jiao Cheng; Zhongli Sha (Journal of Coastal Conservation, 2026)

Beyond pyrolysis optimization: a systematic review revealing feedstock acquisition and methodological standardization as critical barriers to biochar commercialization - R. B. Sherly Priyanka; Uday Shashikumar; Pei-Chien Tsai; Swapnil Gurrani; Gangadhar Andaluri; Cheng-Di Dong; Chyi-How Lay; Yuan-Chung Lin; Vinoth Kumar Ponnusamy (Clean Technologies and Environmental Policy, 2026)

Ensuring consistency in spatially-stratified stock assessment models: An analytical solution for equilibrium population structure with connectivity for age-and size-structured models - Matthew LH. Cheng; Timothy J. Miller; Daniel R. Goethel; Curry J. Cunningham (Fisheries Research, 2026)

Continuous speleothem record from central Tunisia (the Mine cave) reveals climatic events for the last 27 ka - Sahar Ben Hamida; Chedia Zaara Ben Mosbah; Walid Oueslati; Dominique Blamart; Hai Cheng; R. Lawrence Edwards; Matthieu Fournier; Dominique Genty (Quaternary Science Reviews, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Modulation of structural transitions, integrity, and digestibility in deep-defatted pea starch noodles through supplementation with partial defatting of common vetch starch - Ebenezer Asiamah; Yiming Wang; Yan Wang; Dong-Hui Geng; Xin Jia; Monica R. Nemţanu; Dominic Aboagye; Yongqiang Cheng; Na Zhang (Food Research International, 2026)

Exploring the longitudinal links of chemosensory hedonic capacity with appetitive traits and satisfaction with food-related life in Chinese older adults - Jiayi Han; Yueyang Xiao; Peiyi Wang; Yunyi Cheng; Wesley R. Barnhart; Jinbo He (Food Quality and Preference, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Conservation agriculture improves potassium balance in a high potassium input cropping system - M. J. Islam; M. Cheng; U. Kumar; M. Maniruzzaman; S. S. Nasreen; A. Islam; M. E. Haque; M. Jahiruddin; R. W. Bell; M. M. R. Jahangir (Nutrient Cycling in Agroecosystems, 2026)

Assessment of legacy and emerging contaminants in sediment of an Australian deepwater ocean outfall - Sazal Kumar; Megan Andrew-Priestley; Hsuan-Cheng Lu; Frederic D.L. Leusch; Allison C. Luengen; Zoe Rogers; Katie Newton; Geoff R. MacFarlane (Marine Pollution Bulletin, 2026)

Natural anti-tobacco mosaic virus constituents from plants: A review - Junmei Wang; Juxiang Wang; Shanshan Xiao; Yingshun Miao; Zhengxuan Wang; Jueting Liu; Hongwei Wang; Yaping Liu; Hesham R. El-Seedi; Wenbing Zhou; Guiguang Cheng (Pesticide Biochemistry and Physiology, 2026)

Dynamic water delay time estimation using dispatch data for improved inflow forecasting in cascade hydropower reservoirs - Xiong Cheng; Junwen Yang; Bin Luo; Miriam R. Aczel; Wenwu Li; Hao Zhong; Xianshan Li; Shumian Miao (Journal of Hydrology, 2026)

Sidr honey: A comprehensive review of its nutritional value, biological impact, and potential health benefits - Hesham R. El-Seedi; Aida A. Abd El-Wahed; Mahmoud M. Swilam; Abdulraouf M. Amro; Wesam M. Hussein; Guiguang Cheng; Paolo Coghi; Mingquan Guo; Aamer Saeed; Zhiming Guo; Shaden A.M. Khalifa (Food Bioscience, 2026)

Evaluation of multiple inhibitory effects of Paenibacillus polymyxa KM2501-1 on Meloidogyne incognita - Wanli Cheng; Wei Dai; Wen Chen; Xue Yang; Ahmed R. Henawy; Zhengbing Jiang; Minmin Cai; Longyu Zheng; Ziniu Yu; Jibin Zhang (European Journal of Plant Pathology, 2026)

The SPoRC Stock Assessment Package: A Generalized Next‐Generation Platform to Assess Spatial, Age and Sex‐Structured Populations - Matthew LH. Cheng; Daniel R. Goethel; Curry J. Cunningham; Peter‐John F. Hulson; James N. Ianelli; Kristen L. Omori (Fish and Fisheries, 2026)
Fisheries managers increasingly rely on stock assessment models to provide sustainable management advice, which must balance complex and competing objectives. Although assessment models necessitate simplifying assumptions, there is increasing recognition to improve the integration of realistic biological and fishery dynamics. While ongoing and future development of increasingly complex stock assessments requires increased capacity (i.e., time, training, and personnel), there are concerns that the growing demand for assessment advice cannot be adequately fulfilled under current resources. To address these needs, we present the Stochastic Population over Regional Components (SPoRC) model, a modern integrated analysis platform that is generalized, modular and developed in a user‐friendly programming language (R with Template Model Builder, RTMB). Development of SPoRC emphasized consideration of age, sex, and spatial dynamics at the outset, while ensuring the ability to integrate diverse data sources (e.g., catch, abundance indices, age/length compositions and tagging). Moreover, state‐space specification of time‐varying processes through random effects and robust simulation capabilities were primary design features. Here, we highlight SPoRC's utility in cohesively implementing single‐and multi‐region applications, its ability to estimate time‐varying processes as random effects, and the potential to conduct closed‐loop simulations for evaluating the robustness of management procedures. By developing a generalized assessment platform in a user‐friendly R package, we suggest that SPoRC reduces barriers to implementation of next‐generation stock assessment models and facilitates team‐based model development, which will ultimately help improve the capacity to implement stock assessments globally.

Levels of 129I in coastal Pacific Ocean waters from southern California, 2011–2020 and the legacy of Fukushima - A. J. Timothy Jull; Ching-Chih Chang; George S. Burr; Li Cheng; Joellen Russell; Mang Lin; Daniel R. Crocker; Mark Thiemens; Dana Biddulph; Marc W. Caffee; Tom Woodruff; Christopher Glynn; et al. (Frontiers in Marine Science, 2026)
The Fukushima Daiichi Nuclear Power Plant accident released radionuclides directly into the ocean as a result of the Great East Japan Earthquake on March 11, 2011. This material has been transported across the Pacific Ocean and detected in the northeastern Pacific. We began a surface ocean 129 I monitoring program a few months after this disaster in June 2011, with samples from Scripps Pier, La Jolla, California, USA, with the expectation that surface currents originating off the east coast of Japan could eventually carry radionuclides to the La Jolla site. We could not identify a significant distinct signal that can be traced to Fukushima from the record from 2011-2020. We have however recorded a systematic seasonal 129 I time series record that appears to be due to surface circulation variations along the California coast, or perhaps other unexplained effects. We have reported on some of these effects previously, where we summarized results up to 2018. Since then, we have analyzed additional samples obtained during our sampling program for 2018–2020 from Scripps and also report other results collected during 2015–2016 from Newport Beach, CA, which had not been reported. These results support and expand on the previously published dataset.

Seasonal variations in the abundance and distribution of small-sized microplastics in Hong Kong's marine waters - Kai Zhang; Michael C.Y. Cheng; Mengyang Liu; Shaopeng Xu; Yue Ma; Hoi Shan Chau; Yaru Cao; Meng Yan; Wai Thoe; Sunny W.C. Sun; Ron R. Yang; Kenneth M.Y. Leung; et al. (Marine Pollution Bulletin, 2026)

The global proliferation of aquatic, benthic Microcoleus: Taxonomy, distribution, toxin production, ecology, and future directions - Laura T. Kelly; Daniel G. Beach; Joanna R. Blaszczak; Keith Bouma-Gregson; Sydney M. Brown; Haowu Cheng; Janette L. Davidson; Jutta Fastner; Marcus Francis; Andrea Garcia Jimenez; Laurel Genzoli; Ramesh Goel; et al. (Water Research, 2026)

Millennial-scale hydroclimate variability of the Asian monsoon during MIS 9 from stalagmite records - Sinan Wang; Xunlin Yang; Hai Cheng; Wenming Zhou; Guofeng Li; Wanli Xiang; Rui Zhang; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Fair scheduling efficiency benchmarking for sustainability in heterogeneous hydropower systems - Xiong Cheng; Xiaotao Zeng; Qingshe Meng; Mian Wang; Lei Wang; Miriam R. Aczel; Wenwu Li; Xianshan Li; Hao Zhong (Journal of Cleaner Production, 2026)

Species composition, competition, and environmental stress influence early growth dynamics in bottomland forest communities - Olaniyi O. Ajala; Zhongqian Cheng; Jeremy P. Stovall; Kathryn R. Kidd; Brian P. Oswald; Yuhui Weng (Forest Ecology and Management, 2026)

Stepwise defatting of surface and starch-bound lipids improves retrogradation resistance and textural quality of pea starch noodles - Ebenezer Asiamah; Na Zhang; Yiming Wang; Jinxue Zhang; Dong-Hui Geng; Monica R. Nemţanu; Sameh Sharafeldin; Yongqiang Cheng (Food Chemistry, 2026)

Abrupt temperature shifts alter DOM composition and electron transfer capacity: Unraveling the impact of climate extremes on greenhouse gas emissions in Yangtze River floodplain sediments - Junming Wu; Qiong Zhang; Ning-Xin Wang; Giri R. Kattel; Cheng-Gong Yang; Sven Frei; Zhi-Guo Yu (Environmental Research, 2026)

Amylose content of sorghum starches measured by four different methods in relation to molecular structures of sorghum amylose and amylopectin - Dongxing Li; Xiaorong Wu; Scott R. Bean; Yong-Cheng Shi (Carbohydrate Polymers, 2026)

A deep learning approach predicts O3 increase and PM2.5 declines under high emission scenario across the Northern China urban agglomeration - Gangfeng Zhang; Shuo Wang; Jing Xu; Tim R. McVicar; Yun Cheng; Cesar Azorin-Molina; Lorenzo Minola; Nan Wang; Jiang Zhang; Peijun Shi (Urban Climate, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Sustainable PET-derived zwitterionic gels reinforced by ionic liquids for flexible electronic skin sensors - Hui Duan; XiaoQian Yao; Rana R. Neiber; Xingbo Jie; XiuJie Cheng; Jiayu Xin; Qing Zhou; Yi Li; Junli Xu; Dongxia Yan; Yu Zhang; Xingmei Lu (Chemical Engineering Journal, 2026)

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Adapting rodent cued threat conditioning to planarians: Memory acquisition, consolidation, and reconsolidation - Fionnghuala L.J. James; Sayed K. Ahamed; Cheng Yang; Jigme Thinley; Carmelo M. Vicario; Juan J. Canales; Sukhwinder S. Sohal; Richard Wilson; Luke R. Johnson; Vanni Caruso (Behavioural Processes, 2026)

Identifying Headwater Streams across the Conterminous United States - Charles R. Lane; Ellen D’Amico; Jay R. Christensen; Heather E. Golden; Frederick Y. Cheng; John C. Hammond; Admin Husic; Kristin L. Jaeger; C. Nathan Jones; Christa A. Kelleher; Li Li; D. Tyler Mahoney; et al. (Ecosystems, 2026)

WABAD : A world annotated bird acoustic dataset for passive acoustic monitoring - Cristian Pérez‐Granados; Jon Morant; Kevin F. A. Darras; Oscar H. Marín‐Gómez; Irene Mendoza; Miguel A. Muñoz‐Mohedano; Eduardo Santamaría‐García; Giulia Bastianelli; Alba Márquez‐Rodríguez; Michał Budka; Gerard Bota; José M. De la Peña‐Rubio; et al. (Ecology, 2026)
Under the current global biodiversity crisis, there is a need for automated and noninvasive monitoring techniques that can gather large amounts of data cost‐effectively at various ecological scales, from local to large spatial scales. These data can then be analyzed to inform stakeholders and decision‐makers. One such technique is passive acoustic monitoring, which is commonly coupled with automatic identification of animal species based on their sound. Automated sound analyses usually require the training of sound detection and identification algorithms. These algorithms are based on annotated acoustic datasets which mark the occurrence of sounds of species inside sound recordings. However, compiling large annotated acoustic datasets is time‐consuming and requires experts, and therefore, they normally cover reduced spatial, temporal, and taxonomic scales. This data paper presents WABAD, the World Annotated Bird Acoustic Dataset for passive acoustic monitoring. WABAD is designed to provide the public, the research community, and conservation managers with a novel and globally representative annotated acoustic dataset. This database includes 5047 min of audio files annotated to species‐level by local experts with the start and end time and the upper and lower frequencies of each identified bird vocalization in the recordings. The database has a wide taxonomic and spatial coverage, including information on 91,931 vocalizations from 1192 bird species recorded at 72 recording sites in 29 recording locations (mainly countries) and distributed across 13 biomes. WABAD can be used, for example, for developing and/or validating automatic species detection algorithms, answering ecological questions, such as assessing geographical variations on bird vocalizations, or comparing acoustic diversity indices with species‐based diversity indices. The dataset is published under a Creative Commons Attribution 4.0 International license that permits redistribution and reuse on the condition that the original work is properly credited.

Spatial and temporal variations in the distribution of eastern Australian post-orogenic granites and related mineral deposits: metallogenic and tectonic significance - D. L. Huston; Y. Cheng; S. L. Jones; D. C. Champion; M. D. Norman; M. W. Agnew; A. Cross; V. C. Bennett; R. A. Creaser (Australian Journal of Earth Sciences, 2026)

Speleothem-based reconstruction of Holocene changes in monsoonal patterns and environmental conditions in Central Brazil - Marcela Eduarda Della Libera; Julio Cauhy; Cintia Stumpf; Roberto V. Santos; Francisco W. Cruz; Nicolas M. Stríkis; Luciana F. Prado; Jean-Sebastian Moquet; Michael Weber; Rebecca Orrison; Hai Cheng; R. Lawrence Edwards; et al. (Global and Planetary Change, 2026)

d–p–d orbital coupling-driven electronic modulation in CoSe2/TiSe2@Ti3C2T MXene for enhanced supercapacitors and oxygen evolution reaction - Eslam Aboelazm; Mohammad R. Thalji; Mohamad Amin Hamid; Hyeonwook Park; Hassan Zuhaib; Cheng Seong Khe; Chinho Park; Mohamed Shuaib Mohamed Saheed (Chemical Engineering Journal, 2026)

Origin and global spread of an endemic chytrid fungus lineage linked to the bullfrog trade - Luisa P. Ribeiro; Julia R. Ernetti; Joice Ruggeri; Thomas S. Jenkinson; Adeline Loyau; Helen Butler; Tina Cheng; Dirk S. Schmeller; Timothy Y. James; Luís Felipe Toledo (Biological Conservation, 2026)

Identification, sources and accumulation behavior of priority odorants discharged to surface water from stormwater systems with illicit connections - Cheng Ye; Fangyuan Jiang; Feifei Wang; Zoran Kapelan; Zuxin Xu; Michael R. Templeton; Wenhai Chu (Water Research, 2025)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Reliable identification of flood-borne deposits in speleothems using magnetic microscopy - Samuel L. Piascik; Roger R. Fu; Nicolás M. Stríkis; Ricardo I.F. Trindade; Julio Cauhy Rodrigues; Francisco W. Cruz; Gelson F. Souza-Junior; Andrea Borsato; Vitor Azevedo; Plinio Jaqueto; Isabel Tamara Pedron; Perri Thaler; et al. (Quaternary Science Reviews, 2025)

Detailed Asian summer monsoon changes during the Mid Holocene and their teleconnections with the northern high latitudes - Bin Zhao; Yingfang Cui; Kan Zhao; Yongjin Wang; Hai Cheng; R. Lawrence Edwards; Yijia Liang (Quaternary Science Reviews, 2025)

Monsoonal and westerly influences on interglacial calcite deposition and environmental conditions in southern Tibetan Plateau - Haibo Wang; Carlos Pérez-Mejías; Xianyan Wang; Tingyong Li; Can Yang; Hanying Li; Shihao Lei; Youfeng Ning; R. Lawrence Edwards; Hai Cheng (Quaternary Science Reviews, 2025)

Hydrogeochemical characteristics and the monitoring from 2020 to 2023 of hot spring waters in Tatun Volcanic Group, Taiwan - Ju-lien Pi; Hsueh-Yu Lu; Hsiao-Fen Lee; Hung-Chun Chao; Chen-Feng You; Tsung-Ren Peng; Raymond Patrick R. Maximo; Chia-Tai Wu; Ya-Wen Wu; Chung Fang; Cheng-Horng Lin (Journal of Asian Earth Sciences, 2025)

The coupling between monsoon rainfall and Sea Surface Temperature in the subtropical South Atlantic during the Last Glacial Period - Lucas C. Vasconcelos; Francisco W. Cruz; Juan Pablo Bernal; Marília C. Campos; Patrícia Piacsek; José L. Campos; Haiwei Zhang; Nicolás Stríkis; Mathias Vuille; Giselle Utida; Christian Millo; R. Lawrence Edward; et al. (Global and Planetary Change, 2025)

Indian summer monsoon variability across the last 9000 years: New evidence from stalagmites of southwestern China - Yanzhen Li; Chunju Huang; Jianghu Lan; David B. Kemp; James G. Ogg; Ashish Sinha; Lvfan Chen; Xiqian Wang; Huiru Tang; Xu Lin; Khalaf H.M. Abdel-Raheem; Rui Zhang; et al. (Global and Planetary Change, 2025)

Eco-friendly and energy efficient flowable surface modified carbon electrode materials in flow electrode capacitive deionization for heavy metal adsorption and energy recovery - T.M. Subrahmanya; Ya-Ting Chung; Smruthiranjan Nayak; H.K. Makari; Alvin R. Caparanga; Chia-Hsiung Cheng; Wei-Song Hung; Chien-Chieh Hu; Kueir-Rarn Lee; Juin-Yih Lai (Chemosphere, 2025)

Evaluation of multimodel averaging approaches for ensembling evapotranspiration and yield simulations from maize models - Viveka Nand; Zhiming Qi; Liwang Ma; Matthew J. Helmers; Chandra A. Madramootoo; Ward N. Smith; Tiequan Zhang; Tobias K.D. Weber; Elizabeth Pattey; Ziwei Li; Jiaxin Wang; Virginia L. Jin; et al. (Journal of Hydrology, 2025)

From the hive to the brain: synergistic potential of honeybee products with alzheimer’s drugs - Hesham R. El-Seedi; Suzy Salama; Aya A. Shetaia; Mohamed H. Elashal; Aida Abd El-Wahed; Sercan Karav; Aamer Saeed; Mohammad A. Alzahrani; Xiaobo Zou; Lucian Hritcu; Guiguang Cheng; Mohamed F. Salem; et al. (Metabolic Brain Disease, 2025)

Monsoon and hydroclimate evolution during Heinrich Stadial 3 as revealed by stalagmite from Central China - Zhenjun Wang; Shitao Chen; Yongjin Wang; Li Wu; Shaohua Yang; Gongzhe Chen; Zhenqiu Zhang; Yijia Liang; Qingfeng Shao; Hai Cheng; R. Lawrence Edwards (Global and Planetary Change, 2025)

The Maud Belt (East Antarctica) as an accretionary orogen in Rodinia: Isotopic composition, evolution and spatial variation - Cheng-Cheng Wang; Joachim Jacobs; Horst R. Marschall; Sidney Hemming; Guillaume Jacques; Andreas Läufer (Gondwana Research, 2025)

Study on the change of multi-season urban heat island effect from the perspective of urban functional zones - T. Su; X. S. Dou; X. Y. Cui; D. Liu; B. Lei; M. N. Yuan; R. J. Chen; X. Cheng (International Journal of Environmental Science and Technology, 2025)

Hidden markov mark-recapture modeling highlights transboundary exchange for northeast pacific sablefish - Maia Kapur; Luke Rogers; Daniel R. Goethel; Matthew LH. Cheng; Dana Hanselman; Katy Echave; Melissa A. Haltuch; Kendra R. Holt; Philina English; Aaron M. Berger; Brendan Connors (Fisheries Research, 2025)

P30-01 Application of 3Rs Strategies for Existing Chemicals Substances Standard Registration in Taiwan: Case study of Silicon carbide - S.-N. Chen; O. Lautan; Y.-Y. Chen; Y.-L. Yeh; Y.-H. Cheng; C.-C. Tseng; T.-N. Li; Z.-Y. Chen; R.-J. Chen; Y.-J. Wang (Toxicology Letters, 2025)

P10-03 Associations of Urinary Endocrine-Disrupting Chemicals with Obesity and Lipid Metabolism in Children and Adolescents: The Expanded Chinese National Human Biomonitoring (CNHBM) Project - N. Jiang; Q. Chen; B. Cheng; H. Chen; H. Sun; R. Liu (Toxicology Letters, 2025)

Landowners' willingness to accept for sustainable forest management in the Cross-Timbers region, USA - Haotian Cheng; José R. Soto; Andres Susaeta; Aaron Russell; Omkar Joshi (Forest Policy and Economics, 2025)

Intrinsic Functional Connectivity Associated with γ‑Aminobutyric Acid and Glutamate/Glutamine in the Lateral Prefrontal Cortex and Internalizing Psychopathology in Adolescents - Kai Wang; Harry R. Smolker; Mark S. Brown; Hannah R. Snyder; Yu Cheng; Benjamin L. Hankin; Marie T. Banich (Neuroscience Bulletin, 2025)

Are Recommended Fertilizer Rates Able to Maintain Nutrient Balance in Soil and Optimize Crop Profit in Intensive Rice-Based Crop Rotations: Evidence from a 20-Year Study - Utpol Kumar; Miaomiao Cheng; M. Jahedul Islam; M. Maniruzzaman; Shah Shanjida. Nasreen; M. Enamul Haque; Sohela Akhter; M. Jahiruddin; Richard W. Bell; M. M. R. Jahangir (Journal of Soil Science and Plant Nutrition, 2025)

Panmictic Panacea? Demonstrating Good Practices for Developing Spatial Stock Assessments Through Application to Alaska Sablefish ( Anoplopoma fimbria ) - Matthew L. H. Cheng; Craig A. Marsh; Daniel R. Goethel; Peter‐John F. Hulson; Katy Echave; Benjamin C. Williams; Aaron M. Berger; Curry J. Cunningham (Fish and Fisheries, 2025)
Marine species and associated fisheries demonstrate complex spatial dynamics driven by biological, ecosystem and socioeconomic factors and integrating these spatial dynamics into stock assessment models can improve fishery management advice. While preliminary good practices for developing spatial stock assessment models have been proposed, comprehensive demonstrations applying these practices remain limited. Drawing on these good practices, we provide an end‐to‐end demonstration of developing a spatial stock assessment using Alaska sablefish ( Anoplopoma fimbria ). Our demonstration emphasises the utility of high‐resolution data analysis and conceptual models for informing key model structure decisions, the joint development of spatial and spatially‐aggregated models to enhance understanding of population dynamics, and the need for further guidance on integrating tagging data and diagnostic tools in spatial assessments. Spatial models highlighted regional differences in sablefish biomass, recruitment and age structure, but total population estimates generally aligned with outputs from spatially aggregated models. Moreover, the spatial model identified ontogenetic movement patterns for this highly mobile species. Overall, the spatially aggregated model for Alaska sablefish is likely adequate for management advice, but periodic spatial model updates could offer insights into spatial dynamics and regional depletion levels. Thus, we recommend concomitant use of both models: spatially aggregated models for informing population‐wide status, and spatial models for informing spatial fishery dynamics and local depletion. The sablefish application represents one of the first implementations of a spatial stock assessment using recently proposed good practices, serving as a valuable guide for future practitioners by underscoring critical decision points and analyses to address them when developing spatial stock assessments.

EnsembleAge: enhancing epigenetic age assessment with a multi-clock framework - Amin Haghani; Ake T. Lu; Qi Yan; Juan Carlos Izpisua Belmonte; Pradeep Reddy; Victor Cheng; X. William Yang; Nan Wang; Khyobeni Mozhui; Kevin Murach; Alejandro Ocampo; Robert W. Williams; et al. (GeroScience, 2025)
Several widely used epigenetic clocks have been developed for mice and other species, but a persistent challenge remains: different mouse clocks often yield inconsistent results. To address this limitation in robustness, we present EnsembleAge, a suite of ensemble-based epigenetic clocks. Leveraging data from over 200 perturbation experiments across multiple tissues, EnsembleAge integrates predictions from multiple penalized models. Empirical evaluations demonstrate that EnsembleAge outperforms existing clocks in detecting both pro-aging and rejuvenating interventions. Furthermore, we introduce EnsembleAge HumanMouse, an extension that enables cross-species analyses, facilitating translational research between mouse models and human studies. Together, these advances underscore the potential of EnsembleAge as a robust tool for identifying and validating interventions that modulate biological aging.

Annually laminated stalagmite inferred variations of precipitation and temperature in northern China over the last 150 years - Yingying Wei; Yanjun Cai; Xing Cheng; Gang Xue; Kang’en Zhou; Le Ma; Yanbin Lu; Shouyi Huang; Mei He; Hai Cheng; R. Lawrence Edwards (Climate Dynamics, 2025)

Societal responses to cold-season rainfall variability: a speleothem perspective on Byzantine and Hittite climate interactions in Late Holocene Türkiye and southeast Europe - Alistair W. Morgan; Alice R. Paine; Koray Koç; John Haldon; Elisa Hofmeister; Hai Cheng; Okan Tüysüz; Albert Matter; Lawrence R. Edwards; Negar Haghipour; Irka Hajdas; Dominik Fleitmann (Quaternary Science Reviews, 2025)

Effects of Ikaros (IKZF1) gene in the virulence of Marek’s disease virus - Taejoong Kim; Masahiro Niikura; John R. Dunn; Hans H. Cheng; Cari J. Hearn (Veterinary Microbiology, 2025)

Hydrological changes in the East Asian monsoon region around 4.2 ka precisely reconstructed from multi-proxy stalagmites - Chao-Jun Chen; Yao Wu; Jun-Yun Li; Hai-Wei Zhang; Hai Cheng; Chuan-Chou Shen; You-Feng Ning; Dao-Xian Yuan; R. Lawrence Edwards; Jian Zhang; Ting-Yong Li (Quaternary Science Reviews, 2025)

In-situ geotechnical properties of abyssal sediments and implications for environmental impacts of polymetallic nodule mining - Zhenggang Li; Zhou Li; James R. Hein; Yangrui Cheng; Yuwei Liu; Shiquan Lin; Hao Wang; Xibin Han; Yanhui Dong; Fengyou Chu; Xiaohu Li (Marine Geology, 2025)

Comparison of microwave-assisted and hot-air-drying method on the physicochemical properties and eating quality of rice bran noodles - Ping-Hsiu Huang; Yu-Tsung Cheng; Wen-Chien Lu; I-Yu Chiu; Chiun-Chung R. Wang; Po- Hsien Li (Food Bioscience, 2025)

Fast arc retreat in the eastern Mediterranean: constraints from late Campanian forearc deposits (Donousa, Greece) - S. O. Martha; P. Xypolias; C. Cheng; W. Dörr; A. Gerdes; D. C. Hezel; M. Kutzschbach; L. Millonig; H. Schmeling; H. R. Marschall; W. Müller; G. Zulauf (International Journal of Earth Sciences, 2025)
The island of Donousa consists of a variegated metasedimentary sequence cut by arc-type granitoid dykes. Detrital zircon U–Pb ages and the presence of volcanic and ultramafic detritus suggest that the protoliths of the metasedimentary rocks were deposited in a Campanian forearc basin later than 76 Ma. D1 stacking of the forearc deposits occurred at upper crustal levels (P max = 0.4 GPa) with staurolite present as a stable phase. The subsequent isobaric heating led to growth of andalusite followed by D2 extension in the stability field of sillimanite, K-feldspar and high-quartz ( P = 0.3 GPa, T = 660 °C). Based on U–Pb ages of garnet (74.6 + 2.3/ − 2.5 Ma) and zircon (74.0 ± 0.8 Ma), separated from an early monzogranite dyke, the timing of forearc deposition, Buchan metamorphism, D2 extension and dyke emplacement is constrained to a maximum period of 2.6 m.y. in the late Campanian. Cooling below T = ca. 600 °C occurred during the Maastrichtian (71.3 + 0.6/ − 1.3 Ma, U–Pb on titanite) and was followed by D3 folding under greenschist facies conditions. A younger generation of Danian granitoid dykes (64.1 + 0.9/ − 1.4 Ma, U–Pb on titanite; 60 ± 4 Ma, Rb–Sr on muscovite) intruded at higher structural levels and was associated with a pervasive fluid-assisted overprint. The sequence of forearc deposition, burying, Buchan metamorphism, extension, and igneous dyking within < 2.6 m.y. is strong evidence for fast (ca. 4 cm a −1 ) trenchward arc retreat that was probably related to late Campanian subduction accretion and magmatic flare-up. Graphical abstract

Leveraging large language models to compare perspectives on integrating QSP and AI/ML - Ioannis P. Androulakis; Limei Cheng; Carolyn R. Cho; Tongli Zhang (Journal of Pharmacokinetics and Pharmacodynamics, 2025)

Millennial-scale climate variability of the Asian summer monsoon over the last 690,000 years: insights from cave records - Xiaowen Niu; Jian Wang; Le Kang; Youwei Li; Haiwei Zhang; Xiyu Dong; Hanying Li; Lijuan Sha; Liang Yi; Ashish Sinha; Youfeng Ning; Xue Jia; et al. (Science Bulletin, 2025)

Hydroclimate variability in southwest China during Marine Isotope Stage 9: Insights from multi–proxy stalagmite records - Wei Jia; Yan Yang; Hai Cheng; Tingyong Li; Jingyao Zhao; Shaoneng He; Guangxin Liu; Xiao Liu; Lidan Lei; Mingyang Li; R. Lawrence Edwards (Quaternary Science Reviews, 2025)

Rapid Indian Monsoon response to the Younger Dryas event in the Southeastern Tibetan Plateau - Xiqian Wang; Liangcheng Tan; Ashish Sinha; Hai Xu; Haiwei Zhang; Jianghu Lan; Jin Zhang; Tianli Wang; Dong Li; Le Ma; Jingjie Zang; Xing Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Multi-instrument sounding of a Jovian thunderstorm from Juno - Shawn R. Brueshaber; Zhimeng Zhang; John H. Rogers; Gerald Eichstädt; Glenn S. Orton; Davide Grassi; Leigh N. Fletcher; Cheng Li; Shinji Mizumoto; Alessandro Mura; Fabiano Oyafuso; Ramanakumar Sankar; et al. (Icarus, 2025)

Cross-cultural evidence that intergroup conflict heightens preferences for dominant leaders: A 25-country study - Lasse Laustsen; Xiaotian Sheng; M. Ghufran Ahmad; Laith Al-Shawaf; Benjamin Banai; Irena Pavela Banai; Michael Barlev; Nicolas Bastardoz; Alexander Bor; Joey T. Cheng; Anna Chmielińska; Alexandra Cook; et al. (Evolution and Human Behavior, 2025)

Systematics and evolutionary history of raft and nursery‐web spiders (Araneae: Dolomedidae and Pisauridae) - Kuang‐Ping Yu; Ren‐Chung Cheng; Charles R. Haddad; Akio Tanikawa; Brogan L. Pett; Luis N. Piacentini; Ho Yin Yip; Yuya Suzuki; Arnaud Henrard; Christina J. Painting; Cor J. Vink; Eileen A. Hebets; et al. (Zoologica Scripta, 2025)
Pisauridae are a global and heterogeneous assemblage of spider genera with diverse morphologies and lifestyles. So far, the monophyly of Pisauridae and the inclusion of fishing spiders ( Dolomedes ) in this family have not been thoroughly tested. Here, we amend the systematics and classification of these lineages within a UCE phylogenomic framework and through a detailed morphological reappraisal. For estimations of their evolutionary age, we perform and compare outcomes from two divergence estimation approaches, an a posteriori likelihood, and an a priori Bayesian. Phylogenies reject the monophyly of both Pisauridae and Dolomedes : (1) Focal Clade I groups true Pisauridae genera including Pisaura ; (2) Focal Clade II contains Blandinia and is sister to Trechaleidae and Lycosidae; (3) Focal Clade III groups Dolomedes , Megadolomedes , and Ornodolomedes , and is sister to Blandinia , Trechaleidae, and Lycosidae. We therefore propose to delimit Pisauridae by removing Dolomedidae rank resurrected (including Dolomedes , Bradystichus , Megadolomedes , Caledomedes , Mangromedes , Ornodolomedes , and Tasmomedes ) and Blandinia incertae sedis . Likelihood and Bayesian time calibration approaches yield comparable divergence estimations: Pisauridae origin is estimated at 29–40 Ma; Blandinia 21–34 Ma; Dolomedidae 10–17 Ma; Dolomedes 9–16 Ma. Reconstructions suggest that the evolution of terrestrial and web‐building lifestyles from semi‐aquatic ancestors in Pisauridae coincided with cooling and drying climates during the mid‐Miocene, but this was not the case in the few recent cases of terrestrialization in Dolomedes species. This historic reconstruction illustrates how climatic changes, or rapid radiation, can drive lifestyle diversification.

Misspecifying Sex‐Structured Dynamics in Stock Assessment Models - Matthew L. H. Cheng; Daniel R. Goethel; Peter‐John F. Hulson; Michael J. Wilberg; Craig Marsh; Curry J. Cunningham (Fish and Fisheries, 2025)
Sex‐specific variation in population demography and life‐history traits (e.g., growth, natural mortality) is common in many fish populations. Differences in these processes by sex can dictate population dynamics and influence how harvesters interact with the resource. Across various fisheries management systems, stock assessment models (SAMs), which mathematically represent population age and/or size structure, are widely utilised to estimate fish population status and provide sustainable harvest recommendations. However, few studies have examined the implications of alternative modelling assumptions when incorporating sex‐specific dynamics in SAMs. For instance, the impacts of simultaneously ignoring sex‐specific variations in growth, selectivity, and natural mortality on SAM performance have not been explored. In this study, a simulation‐estimation framework was developed for a sexually dimorphic fish population to: (1) assess the consequences of ignoring sexual dimorphism (i.e., growth, natural mortality, and selectivity) and the benefits of using sex‐specific catch data to inform the estimation of these processes, (2) evaluate the implications of incorrect modelling assumptions regarding sex ratio at birth, and (3) develop advice for parameterising observation likelihoods to describe sex‐specific composition data. Correctly parameterising sex‐specific variation in life‐history traits led to more robust population estimates and catch advice. Conversely, SAMs ignoring these variations yielded biased estimates of biomass and harvest recommendations. Collectively, our results underscore that oversimplified assumptions about sex‐specific variations in SAMs can lead to poor management advice. Moreover, results emphasise the need for routine collection of sex‐specific data to support the development of biologically realistic models.

Ecological diversity and metabolic strategies of widespread Marinisomatota in global oceans - Shizheng Xiang; Jianyang Li; Zhen Chen; Ruolin Cheng; Liping Wang; Libo Yu; Guangshan Wei; Xiangyu Guan; Brandon R. Briggs; Gary King; Hongchen Jiang; Zongze Shao (Marine Life Science & Technology, 2025)

Numerical simulations of internal solitary waves interacting with a horizontal cylinder on a slope-shelf - Ming-Hung Cheng; Chih-Min Hsieh; Robert R. Hwang (Ocean Engineering, 2025)

Unveiling the suitability of C-starch as functional food: A pairwise interaction of lipids and polyphenol components (LIPOP) - Ebenezer Asiamah; Monica R. Nemţanu; Mirela Braşoveanu; Dong-Hui Geng; Yiming Wang; Kuaitian Wang; Yongqiang Cheng (Carbohydrate Polymers, 2025)

Spermidine toxicity in Saccharomyces cerevisiae due to mitochondrial complex III deficiency - Wei-Hsuan Su; Jessica J. Smith; Evien Cheng; Megan S. Nishitani; Catherine Y. Choi; Kelsey R. Lee; Alexia Pardos Salzano; Samuel E. Schriner (Biogerontology, 2025)
Spermidine is a naturally occurring polyamine present in all cells and is necessary for viability in eukaryotic cells. The cellular levels of spermidine decline as an organism ages, and its supplementation has been found to extend lifespan in yeast, worms, flies, mice, and human cultured cells. The lifespan extending effect of spermidine is thought to be due to its ability to induce autophagy, a turnover of cellular components. Mitochondrial dysfunction is believed to be a major driver of the aging process. We asked whether spermidine could rescue mitochondrial dysfunction using the yeast Saccharomyces cerevisiae lacking mtDNA (ρ 0 cells) as a model. Not only was spermidine unable to rescue survival in ρ 0 cells, but it appeared to exhibit toxicity resulting in a shortened lifespan. This toxicity appears to not be due to the loss of mitochondrial respiration, elevated oxidative stress, or depleted ATP. Spermidine toxicity could be recapitulated by the genetic or pharmacological inactivation of mitochondrial complex III. It can also be prevented by the impairment of autophagy, through the inactivation of ATG8 , or by impairment of mitochondrial complex II through the inactivation of SDH2 . Spermidine toxicity in ρ 0 cells was present in yeast strains BY4741 and W303, but not D273-10B, demonstrating genetic variance in the phenotype. Thus, caution may be suggested regarding the use of spermidine to alleviate aging in humans. Depending on the genotype of the individual, spermidine could potentially harm the very individuals it is intended to help. Graphical abstract

Environmental Gradients Linked to Human Impacts, Not Species Richness, Drive Regional Variation in Community Stability in Coral Reef Fishes - Cheng‐Han Tsai; Sean R. Connolly (Ecology Letters, 2025)
The stabilising effect of biodiversity on aggregate community properties is well‐established experimentally, but its importance in naturally assembled communities at larger scales requires considering its covariation with other biotic and abiotic factors. Here, we examine the diversity–stability relationship in a 27‐year coral reef fish time series at 39 reefs spanning 10° latitude on Australia's Great Barrier Reef. We find that an apparent relationship between species richness and synchrony of population fluctuations is driven by these two variables' covariation with proximity to coastal influences. Additionally, coral cover volatility destabilises fish assemblages by increasing average population variability but not synchrony, an effect mediated by changes in the intensity of density regulation in the fish community. Our findings indicate that these two environmental factors, both of which are strongly influenced by anthropogenic activity, impact community stability more than diversity does, but by distinct pathways reflecting different underlying community‐dynamic processes.

Corrigendum to “Mid-Holocene hydroclimatic change and hurricane activity in Central America recorded by an Isla de Mona Stalagmite” [Marine Geology 471 (2024) 107289] - Huiru Tang; Liangcheng Tan; Yongli Gao; Jingjie Zang; Le Ma; Yanzhen Li; R. Lawrence Edwards; Hai Cheng; Ashish Sinha; Xiqian Wang; Xing Cheng; Ángel A. Garcia; et al. (Marine Geology, 2025)

Emergency mass disposal of milk: Options and considerations - A. Mahdaviarab; K. Pahlavanyali; R. Cheng; X. Wang; J. Doria; J.A. Howe; J.M. Piñeiro; J. Spencer; Z. Liu (Journal of Environmental Management, 2025)

Understanding how urban communities make trade-offs between forest management and ecosystem service objectives - Haotian Cheng; Francisco J. Escobedo; Alyssa S. Thomas; Jesus Felix De Los Reyes; John N. Ng'ombe; José R. Soto (Forest Policy and Economics, 2025)

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A wheat phytohormone atlas spanning major tissues across the entire life cycle provides novel insights into cytokinin and jasmonic acid interplay - Huanran Yin; Wei Liu; Xin Hu; Jingqi Jia; Mengmeng Liu; Jiaqi Wei; Yikeng Cheng; Xin Gong; Qiang Li; Wenhao Yan; Jizeng Jia; Lifeng Gao; et al. (Molecular Plant, 2025)

Challenges in assessing the effects of environmental governance systems on conservation outcomes - Raphael A. Ayambire; Trina Rytwinski; Jessica J. Taylor; Matthew W. Luizza; Matthew J. Muir; Cynthia Cadet; Derek Armitage; Nathan J. Bennett; Jeremy Brooks; Samantha H. Cheng; Jenny Martinez; Meenakshi Nagendran; et al. (Conservation Biology, 2025)
Effective governance is crucial for the success of conservation projects aimed at protecting wildlife populations and supporting human well‐being. However, few large‐scale, comprehensive syntheses have been conducted on the effects of different environmental governance types on conservation outcomes (i.e., biological and ecological effectiveness or effects of conservation on human well‐being), and clarity on the quantity and quality of evidence remains dispersed and ambiguous. We attempted a systematic map of the evidence on the effectiveness of different governance types to meet desired conservation outcomes in Africa, Asia, and Latin America. However, early in this effort, we observed a general lack of empirical research on the links between governance and conservation outcomes. To fill observed data gaps in the evidence base, we tried triangulating governance data from alternative sources (Protected Planet database) and pooling evidence from research conducted within the same conservation areas. Limited data were contained in the Protected Planet database, and governance types in conservation areas and landscapes were complex, making it difficult to use these approaches to assign governance types to conservation areas. To illustrate our observations from the failed systematic map attempt, we prepared a rapid evidence map that outlines a subset of the evidence base of articles linking governance types and governance principles with conservation outcomes. Only 3.2% (34 of 1067) of the articles we screened directly related conservation outcomes to governance type, and even fewer related governance principles to conservation outcomes. Based on our findings, we recommend improving the evidence base by supporting empirical research and increasing the availability and quality of governance data in freely accessible databases. These recommendations are critical for enhancing understanding of the role of governance in conservation projects and improving conservation outcomes.

Negative emotional eating patterns in Chinese adolescents: A replication and longitudinal extension with latent profile and transition analyses - Hongbin Weng; Wesley R. Barnhart; Hana F. Zickgraf; Urvashi Dixit; Yawei Cheng; Gui Chen; Jinbo He (Appetite, 2025)

A mathematical proof comparing the statistical properties between two common approaches for parameterizing sex-composition likelihoods in fishery stock assessments - Matthew LH. Cheng; Peter-John F. Hulson; Daniel R. Goethel; Curry J. Cunningham (Fisheries Research, 2025)

A web-based histology atlas for the freshwater sentinel species Daphnia magna - Mee S. Ngu; Daniel J. Vanselow; Carolyn R. Zaino; Alex Y. Lin; Jean E. Copper; Margaret J. Beaton; Luisa Orsini; John K. Colbourne; Keith C. Cheng; Khai C. Ang (Science of The Total Environment, 2025)

Mercury deposition in central China from the Last Glacial Maximum to the early Holocene recorded in an accurately-dated stalagmite - Yanzhen Li; Liangcheng Tan; Simin Jin; Hai Xu; Lüfan Chen; David B. Kemp; Ashish Sinha; Le Ma; Chunju Huang; Lawrence R. Edwards; Hai Cheng (Science Bulletin, 2025)

The Palomar twilight survey of ‘Ayló’chaxnim, Atiras, and comets - B.T. Bolin; F.J. Masci; M.W. Coughlin; D.A. Duev; Ž. Ivezić; R.L. Jones; P. Yoachim; T. Ahumada; V. Bhalerao; H. Choudhary; C. Contreras; Y.-C. Cheng; et al. (Icarus, 2025)

Climate controls on speleothem initial 234U/238U ratios in midlatitude settings over two glacial cycles - Carlos Pérez-Mejías; Jian Wang; Youfeng Ning; Ana Moreno; Antonio Delgado-Huertas; R. Lawrence Edwards; Hai Cheng; Heather M. Stoll (Geochimica et Cosmochimica Acta, 2025)

Generation of unpaired electrons to promote electron transfer at the cathode of room-temperature sodium sulfur batteries - Chen Huang; Jing Yu; Yao-Jie Lei; Oleg Usoltsev; Li Gong; Zhibiao Cui; Junshan Li; Canhuang Li; Bingfei Nan; Xuan Lu; Ren He; Xuede Qi; et al. (Chemical Engineering Journal, 2025)

Perceptions of swine industry stakeholders on the use of water-based foam, high-expansion nitrogen foam, and carbon dioxide gas as methods of swine depopulation - Janice Y. Park; Magnus R. Campler; Ting-Yu Cheng; Justin D. Kieffer; Andréia G. Arruda; Madonna E. Benjamin; Dale W. Rozeboom; Andrew S. Bowman (Preventive Veterinary Medicine, 2024)

The role of cryobiology in implementing advanced cell models - Ruth R. Cheng (Cryobiology, 2024)

North Atlantic Heat Transport Convergence Derived from a Regional Energy Budget Using Different Ocean Heat Content Estimates - B. Meyssignac; S. Fourest; Michael Mayer; G. C. Johnson; F. M. Calafat; M. Ablain; T. Boyer; L. Cheng; D. Desbruyères; G. Forget; D. Giglio; M. Kuusela; et al. (Surveys in Geophysics, 2024)
This study uses an oceanic energy budget to estimate the ocean heat transport convergence in the North Atlantic during 2005–2018. The horizontal convergence of the ocean heat transport is estimated using ocean heat content tendency primarily derived from satellite altimetry combined with space gravimetry. The net surface energy fluxes are inferred from mass-corrected divergence of atmospheric energy transport and tendency of the ECMWF ERA5 reanalysis combined with top-of-the-atmosphere radiative fluxes from the clouds and the Earth’s radiant energy system project. The indirectly estimated horizontal convergence of the ocean heat transport is integrated between the rapid climate change-meridional overturning circulation and heatflux array (RAPID) section at 26.5°N (operating since 2004) and the overturning in the subpolar north atlantic program (OSNAP) section, situated at 53°–60°N (operating since 2014). This is to validate the ocean heat transport convergence estimate against an independent estimate derived from RAPID and OSNAP in-situ measurements. The mean ocean energy budget of the North Atlantic is closed to within ± 0.25 PW between RAPID and OSNAP sections. The mean oceanic heat transport convergence between these sections is 0.58 ± 0.25 PW, which agrees well with observed section transports. Interannual variability of the inferred oceanic heat transport convergence is also in reasonable agreement with the interannual variability observed at RAPID and OSNAP, with a correlation of 0.54 between annual time series. The correlation increases to 0.67 for biannual time series. Other estimates of the ocean energy budget based on ocean heat content tendency derived from various methods give similar results. Despite a large spread, the correlation is always significant meaning the results are robust against the method to estimate the ocean heat content tendency.

Retention of Crop Residue Increases Crop Productivity and Maintains Positive Sulfur Balance in Intensive Rice-Based Cropping Systems - Utpol Kumar; M. Cheng; M. J. Islam; M. Maniruzzaman; S. S. Nasreen; M. E. Haque; M. B. Hossain; M. Jahiruddin; R. W. Bell; M. M. R. Jahangir (Journal of Soil Science and Plant Nutrition, 2024)

Phosphorus recycling by mineral-catalyzed ribonucleotide cleavage on iron and manganese oxides - Annaleise R. Klein; Jade J. Basinski; Aurore Niyitanga Manzi; Cynthia X. Cheng; Marcos Sanchez; Wiriya Thongsomboon; Ludmilla Aristilde (Environmental Chemistry Letters, 2024)
Phosphorus is an essential element influencing both food security via plant fertilization, and water pollution through excessive phosphorus use, yet the phosphorus cycle in ecosystems is poorly known. In particular, beyond adsorption, the role of iron and manganese oxides in catalyzing the abiotic dephosphorylation of biomolecules is debated. Here, we studied the reactions of ribonucleotides, containing different phosphate bonding, with goethite, hematite, and birnessite. We employed both high-resolution mass spectrometry of solution species and molecular modeling simulations of ribonucleotide-mineral complexes. Results disclose an up to fivefold preferential hydrolytic cleavage of a phosphoanhydride bond over a phosphoester bond, indicating that mineral-catalyzed reactions reflect the hierarchy reported for the activity of phosphatase enzymes. The fourfold higher catalytic reactivity of goethite and birnessite versus hematite is explained by mineral-specific binding rather than surface area differences. Corresponding simulated adsorbate conformations at the water–mineral interfaces are proposed. Overall, our findings provide new insights on the catalytic recycling of organic phosphorus species by mineral oxides.

Pre-treatments to reduce metabolism in adult green-lipped mussel, Perna canaliculus, in preparation for live transportation - M. C. F. Cheng; L. N. Zamora; N. L. C. Ragg; A. J. R. Hickey; B. J. Dunphy (Aquaculture International, 2024)
Improved sustainability of aquaculture can be achieved by reducing product wastage post-harvest. Aquaculture of the green-lipped mussel, Perna canaliculus , is an important industry for New Zealand, which increasingly exports to live markets. Live transport can keep mussels fresh, but mussels could also be susceptible to handling stresses. To remedy this, pre-treatments that make mussels metabolically depressed, and thus potentially less sensitive to external stressors, were explored. As indicators of depressed metabolism, heart rate (HR), inferred cardiac output (PCO), and relative gaping magnitude (RGM) were simultaneously monitored in mussels experiencing different temperatures, dissolved oxygen levels and anaesthetic (MgCl 2 ) concentrations to compare their efficacy in inducing suppressed metabolism of adult P. canaliculus . We found complex interactions between HR, PCO, and RGM in response to these conditions; however, overall, these response variables were significantly correlated. Mussels showed depressed HR and PCO by up to 100% at 4 °C within 2 h, with correspondingly decreased RGM of up to 48%. Similarly, mussels immersed in 40 g L −1 MgCl 2 suppressed HR by up to 97%, accompanied by up to 76% decrease in PCO, and a slight increase in RGM (11%) after 2 h. While responses were variable, low DO levels suppressed HR by up to 50%, yet PCO and RGM increased two- and threefold relative to control groups. The results of the present study indicated that 4 °C and 40 g MgCl 2 L −1 were more effective conditions as pre-treatments than low dissolved oxygen lower the metabolism of P. canaliculus before live transport.

Successful Invasion Into New Environments Without Evidence of Rapid Adaptation by a Predatory Marine Gastropod - Blair P. Bentley; Brian S. Cheng; Reid S. Brennan; John D. Swenson; Jamie L. Adkins; Andrew R. Villeneuve; Lisa M. Komoroske (Molecular Ecology, 2024)
Invasive species with native ranges spanning strong environmental gradients are well suited for examining the roles of selection and population history in rapid adaptation to new habitats, providing insight into potential evolutionary responses to climate change. The Atlantic oyster drill ( Urosalpinx cinerea ) is a marine snail whose native range spans the strongest coastal latitudinal temperature gradient in the world, with invasive populations established on the US Pacific coast. Here, we leverage this system using genome‐wide SNPs and environmental data to examine invasion history and identify genotype–environment associations indicative of local adaptation across the native range, and then assess evidence for allelic frequency shifts that would signal rapid adaptation within invasive populations. We demonstrate strong genetic structuring among native regions which aligns with life history expectations, identifying southern New England as the source of invasive populations. Then, we identify putatively thermally adaptive loci across the native range but find no evidence of allele frequency shifts in invasive populations that suggest rapid adaptation to new environments. Our results indicate that while these loci may underpin local thermal adaptation in their native range, selection is relaxed in invasive populations, perhaps due to complex polygenic architecture underlying thermal traits and/or standing capacity for phenotypic plasticity. Given the prolific invasion of Urosalpinx , our study suggests population success in new environments is influenced by factors other than selection on standing genetic variation that underlies local adaptation in the native range and highlights the importance of considering population history and environmental selection pressures when evaluating adaptive capacity.

Understanding plant–soil interactions underpins enhanced sustainability of crop production - Xin Wang; Lingyun Cheng; Chuanyong Xiong; William R. Whalley; Anthony J. Miller; Zed Rengel; Fusuo Zhang; Jianbo Shen (Trends in Plant Science, 2024)

Hematite enhances microbial autotrophic nitrate removal in carbonate and phosphate-rich environments by increasing Fe(II) activity - Mingliang Long; Jiaxi Zhu; Xinxin Wang; Shiwen Hu; Juntao Zhang; Kuan Cheng; Tongxu Liu; Wei Liu; John R. Reinfelder; Yundang Wu; Fangbai Li (Science of The Total Environment, 2024)

Multicentennial-scale coupling of the East Asian monsoon to North Atlantic climates during the Last Glacial Maximum - Yingfang Cui; Yijia Liang; Kan Zhao; Yongjin Wang; Zhenqiu Zhang; Quan Wang; Zhenjun Wang; Jianshun Chen; Hai Cheng; R. Lawrence Edwards (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Corrigendum to “Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the industrial revolution recorded by high-resolution stalagmites” [Global and Planetary Chang, 232 (2024) 104337] - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Topological clustering in investigating spatial patterns of particulate matter between air quality monitoring stations in malaysia - Nur Fariha Syaqina Zulkepli; Vine Nwabuisi Madukpe; Mohd Salmi Md Noorani; Mohd Aftar Abu Bakar; R. U. Gobithaasan; Ooi Cheng Jie (Air Quality, Atmosphere & Health, 2024)

Predation on Live and Artificial Insect Prey Shows Different Global Latitudinal Patterns - Elena L. Zvereva; Benjamin Adroit; Tommi Andersson; Craig R. A. Barnett; Sofia Branco; Bastien Castagneyrol; Giancarlo Maria Chiarenza; Wesley Dáttilo; Ek del‐Val; Jan Filip; Jory Griffith; Anna L. Hargreaves; et al. (Global Ecology and Biogeography, 2024)
Aim Long‐standing theory predicts that the intensity of biotic interactions increases from high to low latitudes. Studies addressing geographic variation in predation on insect prey have often relied on prey models, which lack many characteristics of live prey. Our goals were to explore global latitudinal patterns of predator attack rates on standardised live insect prey and to compare the patterns in predation on live insects with those on plasticine prey models. Location Global forested areas. Time Period 2021–2023. Major Taxa Arthropods, birds. Methods We measured predation rates in 43 forested locations distributed across five continents from 34.1° S to 69.5° N latitude. At each location, we exposed 20 sets of three bait types, one set per tree. Each set included three live fly larvae (maggots), three live fly puparia and three plasticine models of the puparia. We used glue rings to isolate half of the sets from non‐flying predators. Results Arthropod attack rates on plasticine prey decreased linearly from low to high latitudes, whereas attack rates on maggots had a U shaped distribution, with the lowest predation rates at temperate latitudes and the highest rates at tropical and boreal latitudes. This difference emerged from intensive predator attacks on live maggots, but not on plasticine models, in boreal sites. Site‐specific attack rates of arthropod predators on live and plasticine prey were not correlated. In contrast, bird attack rates on live maggots and plasticine models were positively correlated, but did not show significant latitudinal changes. Main Conclusions Latitudinal patterns in predation differ between major groups of predators and between types of prey. Poleward decreases in both arthropod and combined arthropod and bird predation on plasticine models do not mirror patterns of predation on our live prey, the latter likely reflecting real patterns of predation risk better than do patterns of attack on artificial prey.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Base metals recovery from waste printed circuit board leachate using biogenic hydrogen sulfide gas - Jonovan Van Yken; Naomi J. Boxall; Ka Yu Cheng; Aleksandar N. Nikoloski; Navid R. Moheimani; Anna H. Kaksonen (Hydrometallurgy, 2024)

Comparing individual and collective valuation of ecosystem service tradeoffs: A case study from montane forests in southern California, USA - Haotian Cheng; Francisco J. Escobedo; Alyssa S. Thomas; Jesus Felix De Los Reyes; José R. Soto (Ecosystem Services, 2024)

Green directional conversion of food waste into glycerol in a two-step differentiation enzymolysis and facultative fermentation using Saccharomyces cerevisiae: Performance assessment and mechanism - Siyu Zhu; Sinuo Li; Eldon R. Rene; Xinhui Cheng; Weifang Ma (Biomass and Bioenergy, 2024)

Natural compounds-based nanomedicines for cancer treatment: Future directions and challenges - Tatiana Andreani; Ruoyu Cheng; Khalil Elbadri; Claudio Ferro; Thacilla Menezes; Mayara R. dos Santos; Carlos M. Pereira; Hélder A. Santos (Drug Delivery and Translational Research, 2024)
Several efforts have been extensively accomplished for the amelioration of the cancer treatments using different types of new drugs and less invasives therapies in comparison with the traditional therapeutic modalities, which are widely associated with numerous drawbacks, such as drug resistance, non-selectivity and high costs, restraining their clinical response. The application of natural compounds for the prevention and treatment of different cancer cells has attracted significant attention from the pharmaceuticals and scientific communities over the past decades. Although the use of nanotechnology in cancer therapy is still in the preliminary stages, the application of nanotherapeutics has demonstrated to decrease the various limitations related to the use of natural compounds, such as physical/chemical instability, poor aqueous solubility, and low bioavailability. Despite the nanotechnology has emerged as a promise to improve the bioavailability of the natural compounds, there are still limited clinical trials performed for their application with various challenges required for the pre-clinical and clinical trials, such as production at an industrial level, assurance of nanotherapeutics long-term stability, physiological barriers and safety and regulatory issues. This review highlights the most recent advances in the nanocarriers for natural compounds secreted from plants, bacteria, fungi, and marine organisms, as well as their role on cell signaling pathways for anticancer treatments. Additionally, the clinical status and the main challenges regarding the natural compounds loaded in nanocarriers for clinical applications were also discussed. Graphical abstract

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

A new LED-based extinction tomography method for measurement of aerosol surface area - Liam Milton-McGurk; Agisilaos Kourmatzis; Hak-Kim Chan; Shaokoon Cheng; Assaad R. Masri; Dino Farina (Journal of Aerosol Science, 2024)

Development of corrosion-fatigue analysis method of cable hangers in tied-arch bridges considering train-bridge interaction - Y.F. Duan; S.K. Wu; H.M. Zhang; R. Zhang; C.B. Yun; J.J.R. Cheng; S.M. Wang (Engineering Structures, 2024)

Response of Permian sediment provenance conversion in Hainan Island to the closure of the Eastern Paleo-Tethys Ocean - Z. J. Xu; S. Y. Gao; J. T. Kong; R. H. Cheng (Australian Journal of Earth Sciences, 2024)

Microplastics in Hong Kong's marine waters: Impact of rainfall and Pearl River discharge - Kai Zhang; Michael C.Y. Cheng; Mengyang Liu; Shaopeng Xu; Yue Ma; Hoi Shan Chau; Luoluo Chen; Yaru Cao; Meng Yan; Xiangrong Xu; Wai Thoe; Sunny W.C. Sun; et al. (Marine Pollution Bulletin, 2024)

Orbital- and millennial-scale hydroclimate changes in central China during the last glacial period - Quan Wang; Kan Zhao; Yongjin Wang; Jianshun Chen; Yijia Liang; Yingfang Cui; Qingfeng Shao; Xiumin Zhai; Zhenqiu Zhang; Xinggong Kong; Hai Cheng; R. Lawrence Edwards; et al. (Quaternary Science Reviews, 2024)

Pyrrhotites in asteroid 162173 Ryugu: Records of the initial changes on their surfaces with aqueous alteration - Hiroharu Yui; Shu-hei Urashima; Morihiko Onose; Mayu Morita; Shintaro Komatani; Izumi Nakai; Yoshinari Abe; Yasuko Terada; Hisashi Homma; Kazuko Motomura; Kiyohiro Ichida; Tetsuya Yokoyama; et al. (Geochimica et Cosmochimica Acta, 2024)

Wheat bran layers: composition, structure, fractionation, and potential uses in foods - Zhongwei Chen; Andrew L. Mense; Lauren R. Brewer; Yong-Cheng Shi (Critical Reviews in Food Science and Nutrition, 2024)

Reliability and Validity of a Theory-Based Determinants of Eating and Physical Activity Behaviors Questionnaire for Chinese Elementary School Children - Yadi Zhang; Cheng Li; Yandi Zhu; Isobel R. Contento; Pamela Ann Koch; Qian Yang; Qinyu Dang; Zhuo Hu; Yuchen Wei; Zhaoyang Chen; Huanling Yu (Journal of Nutrition Education and Behavior, 2024)

Major source categories of PM2.5 oxidative potential in wintertime Beijing and surroundings based on online dithiothreitol-based field measurements - Rico K.Y. Cheung; Lu Qi; Manousos I. Manousakas; Joseph V. Puthussery; Yan Zheng; Theodore K. Koenig; Tianqu Cui; Tiantian Wang; Yanli Ge; Gaoyuan Wei; Yu Kuang; Mengshuang Sheng; et al. (Science of The Total Environment, 2024)

Improvement of biotic nitrate reduction in constructed photoautotrophic biofilm-soil microbial fuel cells - Yu Cheng; Jue Ding; Jiahui Wan; Li Tang; Akaninyene Joseph; Muhammad Usman; Ningyuan Zhu; Yanxia Zhang; Han Sun; Eldon R. Rene; Marton Lendvay; Yiping Li (Journal of Environmental Management, 2024)

Physicochemical properties of Dioscorea alata Tainung No. 1 and 2 via different drying methods and application on the frozen tangyuan - Ping-Hsiu Huang; Yu-Tsung Cheng; Shu-Ju Chen; Wen-Chien Lu; Po-Yuan Chiang; Wen-Pei Cheng; Chiun-Chuang R. Wang; Po-Hsien Li (Food Bioscience, 2024)

Restoring ecological function: Interactions between vertebrates and latrines in a reintroduced population of Rhinoceros unicornis - Balram Awasthi; Kim R. McConkey; Sasith Tharanga Aluthwattha; Cheng Chen; Jin Chen (Biological Conservation, 2024)

Investigating the uses of machine learning algorithms to inform risk factor analyses: The example of avian infectious bronchitis virus (IBV) in broiler chickens - Magnus R. Campler; Ting-Yu Cheng; Chang-Won Lee; Charles L. Hofacre; Geoffrey Lossie; Gustavo S. Silva; Mohamed M. El-Gazzar; Andréia G. Arruda (Research in Veterinary Science, 2024)

Mid-Holocene hydroclimatic change and hurricane activity in Central America recorded by an Isla de Mona Stalagmite - Huiru Tang; Liangcheng Tan; Yongli Gao; Jingjie Zang; Le Ma; Yanzhen Li; R. Lawrence Edwards; Hai Cheng; Ashish Sinha; Xiqian Wang; Xing Cheng; Ángel A. Garcia; et al. (Marine Geology, 2024)

Incorporating Occupant cooling behaviors into novel thermal comfort models for residential demand response - Weilin Li; Lixiang Cheng; Wenhai Sui; Sisi Chen; Jiayin Zhu; Liu Yang; Joe R. Zhao (Energy and Buildings, 2024)

A rice GT61 glycosyltransferase possesses dual activities mediating 2-O-xylosyl and 2-O-arabinosyl substitutions of xylan - Ruiqin Zhong; Dayong Zhou; Dennis R. Phillips; Earle R. Adams; Lirong Chen; John P. Rose; Bi-Cheng Wang; Zheng-Hua Ye (Planta, 2024)

On the brink of explosion? Identifying the source and potential spread of introduced Zosterops white-eyes in North America - Devon A. DeRaad; Marlon E. Cobos; Natalie R. Hofmeister; Lucas H. DeCicco; Madhvi X. Venkatraman; Isao Nishiumi; Bailey McKay; Fa-Sheng Zou; Kazuto Kawakami; Chang-Hoe Kim; Ruey-Shing Lin; Cheng-Te Yao; et al. (Biological Invasions, 2024)

Characterization of organic vapors by a Vocus proton-transfer-reaction mass spectrometry at a mountain site in southeastern China - Yi Zhang; Weiqi Xu; Wei Zhou; Yan Li; Zijun Zhang; Aodong Du; Hongqin Qiao; Ye Kuang; Lanzhong Liu; Zhiqiang Zhang; Xiao He; Xueling Cheng; et al. (Science of The Total Environment, 2024)

Investigating speleothem magnetism as a proxy for dust mobilization and rainfall - Kimberly Hess; Roger R. Fu; Samuel Piascik; Nicolas M. Stríkis; Ricardo I.F. Trindade; Tyler Kukla; Alec R. Brenner; Plinio Jaqueto; Michail I. Petaev; Francisco W. Cruz; Placido Fabricio Silva Melo Buarque; Carlos Pérez-Mejías; et al. (Quaternary Science Reviews, 2024)

Conservation agriculture improves yield and potassium balance in intensive rice systems - M. J. Islam; M. Cheng; U. Kumar; M. Maniruzzaman; S. S. Nasreen; M. B. Hossain; M. E. Haque; M. Jahiruddin; R. W. Bell; M. M. R. Jahangir (Nutrient Cycling in Agroecosystems, 2024)

Exogenous modification of EL-4 T cell extracellular vesicles with miR-155 induce macrophage into M1-type polarization - Bikash R. Giri; Shun Li; Guofeng Cheng (Drug Delivery and Translational Research, 2024)

Uncovering the magnitude of African pangolin poaching with extensive nanopore DNA genotyping of seized scales - Darren Yeo; Amy H. J. Chan; Kum Chew Hiong; Jasmine Ong; Jun Yuan Ng; Jie Min Lim; Wendy Zhang; Sara R. Lim; Charlene J. Fernandez; Anna M‐S. Wong; Benjamin P. Y‐H. Lee; Max D. Y. Khoo; et al. (Conservation Biology, 2024)
Trade in pangolins is illegal, and yet tons of their scales and products are seized at various ports. These large seizures are challenging to process and comprehensively genotype for upstream provenance tracing and species identification for prosecution. We implemented a scalable DNA barcoding pipeline in which rapid DNA extraction and MinION sequencing were used to genotype a substantial proportion of pangolin scales subsampled from 2 record shipments seized in Singapore in 2019 (37.5 t). We used reference sequences to match the scales to phylogeographical regions of origin. In total, we identified 2346 cytochrome b ( cytb ) barcodes of white‐bellied ( Phataginus tricuspis ) (from 1091 scales), black‐bellied ( Phataginus tetradactyla ) (227 scales), and giant ( Smutsia gigantea ) (1028 scales) pangolins. Haplotype diversity was higher for P. tricuspis scales (121 haplotypes, 66 novel) than that for P. tetradactyla (22 haplotypes, 15 novel) and S. gigantea (25 haplotypes, 21 novel) scales. Of the novel haplotypes, 74.2% were likely from western and west‐central Africa, suggesting potential resurgence of poaching and newly exploited populations in these regions. Our results illustrate the utility of extensively subsampling large seizures and outline an efficient molecular approach for rapid genetic screening that should be accessible to most forensic laboratories and enforcement agencies.

Measuring ecosystem services and ecological sensitivity for comprehensive conservation in Giant Panda National Park - Cheng Li; Rong Hou; Ziqiang Bao; Wei Wu; Jacob R. Owens; Wenlei Bi; Qiang Xu; XiaoDong Gu; Zuofu Xiang; Dunwu Qi (Conservation Biology, 2024)
China announced the development of its first 5 national parks in 2021, the primary objective of which is to conserve the natural state and integrity of natural ecosystems. As such, ecosystem services and biodiversity levels are crucial assessment factors for the parks. For Giant Panda National Park (GPNP), we evaluated ecological sensitivity based on water and soil erosion and rocky desertification; ecosystem services based on headwater conservation, soil and water conservation, and biodiversity conservation; and presence of giant panda ( Ailuropoda melanoleuca ) and sympatric species (e.g., takin [ Budorcas taxicolor ], Asiatic black bear [ Ursus thibetanus ]) habitat suitability derived from niche modeling to identify the ecosystem status and assess ecological problems within the park. From our results, we proposed ecologically critical areas to target to meet the park's goals. The suitable habitat for pandas and sympatric species encompassed 62.98% of the park and occurred mainly in the Minshan Mountains. One quarter of the total area (25.67%) contained areas important for ecosystem services. Ecologically sensitive and extremely sensitive areas covered 88.78% of the park and were distributed mainly in Qionglaishan and Minshan Mountains. This coverage indicated that there was much habitat for pandas and sympatric species but that the ecosystems in GPNP are vulnerable. Therefore, ecologically critical areas encompassed all suitable habitats for all the species examined and areas important and extremely important to ecosystem service provision,ecologically sensitive and extremely sensitive areas, encompassed 15.17% of panda habitat, accounted for 16.37% of the GPNP area, and were distributed mainly in the Minshan Mountains. Our results indicated where conservation efforts should be focused in the park and that by identifying ecologically critical areas managers can provide targeted protection for wildlife habitat and ecosystems and effectively and efficiently protect the composite ecosystem. Additionally, our methods can be used to inform development of new national parks.

Addressing complex fleet structure in fishery stock assessment models: Accounting for a rapidly developing pot fishery for Alaska sablefish (Anoplopoma fimbria) - Matthew L.H. Cheng; Daniel R. Goethel; Curry J. Cunningham (Fisheries Research, 2024)

Ultraviolet spectrum reveals the presence of ozone on Jupiter's moon Callisto - R. Ramachandran; J.K. Meka; K.K. Rahul; W. Khan; J.-I. Lo; B.-M. Cheng; D.V. Mifsud; B.N. Rajasekhar; A. Das; H. Hill; P. Janardhan; Anil Bhardwaj; et al. (Icarus, 2024)

Effect of iron sources on methane production and phosphorous transformation in an anaerobic digestion system of waste activated sludge - Yunfei Yang; Xiang Cheng; Eldon R. Rene; Bin Qiu; Qian Hu (Bioresource Technology, 2024)

Electromechanical Response of Mesenteric Ischemia Defined Through Simultaneous High-Resolution Bioelectrical and Video Mapping - Sachira Kuruppu; Leo K. Cheng; Timothy R. Angeli-Gordon; Recep Avci; Niranchan Paskaranandavadivel (Annals of Biomedical Engineering, 2024)

Wave Energy Conversion through Oscillating Water Columns: A Review - R. Gayathri; Jen-Yi Chang; Chia-Cheng Tsai; Tai-Wen Hsu (Journal of Marine Science and Engineering, 2024)
An oscillating water column (OWC) is designed for the extraction and conversion of wave energy into usable electrical power, rather than being a standalone renewable energy source. This review paper presents a comprehensive analysis of the mathematical modeling approaches employed in OWC systems, aiming to provide an in-depth understanding of the underlying principles and challenges associated with this innovative technology. A prominent classification within the realm of wave energy devices comprises OWC systems, which exhibit either fixed or floating configurations. OWC devices constitute a significant proportion of the wave energy converter prototypes currently operational offshore. Within an OWC system, a hollow structure, either permanently fixed or floating, extends below the water’s surface, creating an enclosed chamber where air is captured over the submerged inner free surface. This comprehensive study offers a thorough assessment of OWC technology in conjunction with air turbines. Additionally, the investigation delves into theoretical, computational, and experimental modeling techniques employed for analyzing OWC converters. Moreover, this review scrutinizes theoretical, computational, and experimental modeling methodologies, providing a holistic understanding of OWC converters. Ultimately, this work contributes a thorough assessment of OWC technology’s current state, accentuating its potential for efficient wave energy extraction and suggesting future research avenues.

An integrated study of constraining the initial 230Th of a stalagmite and its implications - Shouyi Huang; Yanjun Cai; Hai Cheng; Gang Xue; Xing Cheng; Mei He; Ruoxin Li; Le Ma; Yingying Wei; Yanbin Lu; Ling Yang; R. Lawrence Edwards (Quaternary Geochronology, 2024)

Pervasive aqueous alteration in the early Solar System revealed by potassium isotopic variations in Ryugu samples and carbonaceous chondrites - Yan Hu; Frédéric Moynier; Wei Dai; Marine Paquet; Tetsuya Yokoyama; Yoshinari Abe; Jérôme Aléon; Conel M. O'D. Alexander; Sachiko Amari; Yuri Amelin; Ken-ichi Bajo; Martin Bizzarro; et al. (Icarus, 2024)

PARSIFAL: A toolkit for triple-GEM parametrized simulation - A. Amoroso; R. Baldini Ferroli; I. Balossino; M. Bertani; D. Bettoni; F. Bianchi; A. Bortone; A. Calcaterra; S. Cerioni; W. Cheng; G. Cibinetto; A. Cotta Ramusino; et al. (Computer Physics Communications, 2024)

Effectiveness of dietary heat-killed Bacillus subtilis harboring plasmid containing 60 copies of CpG-ODN 1668 against Vibrio harveyi in Penaeus vannamei - Wahyu Purbiantoro; Vinh Huynh-Phuoc; B. R. J. Castillo-Corea; Omkar Vijay Byadgi; Ta-Chih Cheng (Veterinary Research Communications, 2024)

Effects of field-aging on the impact of biochar on herbicide fate and microbial community structure in the soil environment - Hongguang Cheng; Dan Xing; Gratien Twagirayezu; Shan Lin; Shangyi Gu; Chenglong Tu; Paul W. Hill; David R. Chadwick; Davey L. Jones (Chemosphere, 2024)

Temporal and spatial variations in body mass and thermogenic capacity associated with alterations in the gut microbiota and host transcriptome in mammalian herbivores - Shien Ren; Liangzhi Zhang; Xianjiang Tang; Yaqi Zhao; Qi Cheng; John R. Speakman; Yanming Zhang (Science of The Total Environment, 2024)

Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the Industrial Revolution recorded by high-resolution stalagmites - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Simulating synergistic effects of climate change and conservation practices on greenhouse gas emissions and crop growth in long-term maize cropping systems - Haomiao Cheng; Qilin Yu; Zhiming Qi; Melissa S. Bukovsky; Lulin Xue; Virginia L. Jin; Liwang Ma; R. Daren Harmel; Xiaoping Chen; Shu Ji; Lingzhan Miao; Shaoyuan Feng (Computers and Electronics in Agriculture, 2023)

Long-term spatiotemporal variations in surface NO2 for Beijing reconstructed from surface data and satellite retrievals - Zixiang Zhao; Yichen Lu; Yu Zhan; Yuan Cheng; Fumo Yang; Jeffrey R. Brook; Kebin He (Science of The Total Environment, 2023)

Economically optimal hydropower development with uncertain climate change - Benxi Liu; Shengli Liao; Jay R. Lund; Xiaoyu Jin; Chuntian Cheng (Journal of Hydrology, 2023)

Ecological implications of plant clonality - Sergio R. Roiloa; Wei Xue; Bi-Cheng Dong; Fei-Hai Yu (Flora, 2023)

Evaluation of oxytetracycline leaching from pregelatinized starch‐coated medicated fish feed - A. R. Marques; T. H. Cheng; K. Y. Man; K. P. Cheng; K. B. Cheung; S. St‐Hilaire (Journal of Fish Diseases, 2023)
The rapid growth and intensification of aquaculture industries have led to an increased use of antibiotics. Consequently, growing concerns have mounted over the environmental contamination of these drugs from medicated feeds and the risk that this poses for antimicrobial resistance. To circumvent environmental leaching, farmers topcoat medicated feeds with oil; however, this only partially addresses the issue. This study investigated the potential of food‐grade pregelatinized corn starch (PGS) as a second top‐coating agent to reduce oxytetracycline (OTC) leaching from the hand‐mixed medicated feed. We immersed top‐coated medicated feeds for different periods of time and measured the concentration of OTC in the water to determine leaching. We found a significantly lower level of OTC in water samples collected from the PGS‐coated medicated feed compared to the non‐PGS‐coated medicated feed, with concentrations of OTC approximately 4 and 2.6 times the latter after 5 min and 2 h of water immersion, respectively. We also fed PGS‐coated antibiotic feed to jade perch to determine if fish accepted the top‐coating and whether they absorbed the OTC. Results from a feeding trial suggested no difference in palatability between PGS and non‐PGS‐coated medicated feed. We also found that muscle tissue from fish fed with the aforementioned diets had similar levels of OTC concentrations, suggesting that PGS coating does not alter the gastrointestinal absorption of this medication. From our experiment, we conclude that PGS is potentially a new top‐coating agent to reduce leaching in hand‐mixed OTC medicated feed.

Vascular senescence and leak are features of the early breakdown of the blood–brain barrier in Alzheimer’s disease models - Ka Ka Ting; Paul Coleman; Hani Jieun Kim; Yang Zhao; Jocelyne Mulangala; Ngan Ching Cheng; Wan Li; Dilini Gunatilake; Daniel M. Johnstone; Lipin Loo; G. Gregory Neely; Pengyi Yang; et al. (GeroScience, 2023)
Alzheimer’s disease (AD) is an age-related disease, with loss of integrity of the blood–brain barrier (BBB) being an early feature. Cellular senescence is one of the reported nine hallmarks of aging. Here, we show for the first time the presence of senescent cells in the vasculature in AD patients and mouse models of AD. Senescent endothelial cells and pericytes are present in APP/PS1 transgenic mice but not in wild-type littermates at the time of amyloid deposition. In vitro, senescent endothelial cells display altered VE-cadherin expression and loss of cell junction formation and increased permeability. Consistent with this, senescent endothelial cells in APP/PS1 mice are present at areas of vascular leak that have decreased claudin-5 and VE-cadherin expression confirming BBB breakdown. Furthermore, single cell sequencing of endothelial cells from APP/PS1 transgenic mice confirms that adhesion molecule pathways are among the most highly altered pathways in these cells. At the pre-plaque stage, the vasculature shows significant signs of breakdown, with a general loss of VE-cadherin, leakage within the microcirculation, and obvious pericyte perturbation. Although senescent vascular cells were not directly observed at sites of vascular leak, senescent cells were close to the leak area. Thus, we would suggest in AD that there is a progressive induction of senescence in constituents of the neurovascular unit contributing to an increasing loss of vascular integrity. Targeting the vasculature early in AD, either with senolytics or with drugs that improve the integrity of the BBB may be valid therapeutic strategies.

Identification and characterisation of taste-enhancing peptides from oysters (Crassostrea gigas) via the Maillard reaction - Baifeng Fu; Xianbing Xu; Xin Zhang; Shuzhen Cheng; Hesham R. El-Seedi; Ming Du (Food Chemistry, 2023)

Accelerating evidence-informed decision-making in conservation implementing agencies through effective monitoring, evaluation, and learning - Shauna L. Mahajan; Lydia Tanner; Gabby Ahmadia; Hannah Becker; Nicole DeMello; Robert Fidler; Alastair R. Harborne; Arundhati Jagadish; Morena Mills; Paul Cairney; Samantha Cheng; Brandie Fariss; et al. (Biological Conservation, 2023)

Investigation of strain localization in sheared granular layers using 3-D discrete element modeling - Chien-Cheng Hung; André R. Niemeijer; Amir Raoof; Thomas Sweijen (Tectonophysics, 2023)

Particulate matter, traffic-related air pollutants, and circulating C-reactive protein levels: The Multiethnic Cohort Study - Meera Sangaramoorthy; Juan Yang; Chiuchen Tseng; Jun Wu; Beate Ritz; Timothy V. Larson; Scott Fruin; Daniel O. Stram; Sung-shim Lani Park; Adrian A. Franke; Lynne R. Wilkens; Jonathan M. Samet; et al. (Environmental Pollution, 2023)

Stable chromium isotope compositions of hydrogenetic ferromanganese crusts potentially linked to primary productivity - Xiangli Wang; Jian-Ming Zhu; Guangliang Wu; Wenjing Liu; Cheng Lin; Wei Yang; Zhifang Xu; James R. Hein (Chemical Geology, 2023)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

The spatio-temporal pattern of Asian summer monsoon during glacial Termination II recorded by Chinese stalagmite δ18O - Wei Jia; Pingzhong Zhang; Xianfeng Wang; Shaoneng He; Guangxin Liu; Hongyu Shi; Binggui Cai; Shufang Yuan; Wenfei Zhang; Ruitao Deng; Leilei Zhang; Tao Gao; et al. (Quaternary Science Reviews, 2023)

Refinement of water-based foam depopulation procedures for finisher pigs during field conditions: Welfare implications and logistical aspects - Magnus R. Campler; Ting-Yu Cheng; Andréia G. Arruda; Mark Flint; Justin D. Kieffer; Brad Youngblood; Andrew S. Bowman (Preventive Veterinary Medicine, 2023)

Environmental optima for common diatoms from Ontario lakes along gradients of lakewater pH, total phosphorus concentration, and depth - Matthew P. Duda; Branaavan Sivarajah; Kathleen M. Rühland; Andrew M. Paterson; Jennifer L. Barrow; Yuanyu Cheng; Elizabeth J. Favot; Kristopher R. Hadley; Roland I. Hall; Kathryn E. Hargan; Clare Nelligan; Euan D. Reavie; et al. (Journal of Paleolimnology, 2023)

Biases in wind speed measurements due to anemometer changes - Cesar Azorin-Molina; Amir Ali Safaei Pirooz; Shalenys Bedoya-Valestt; Eduardo Utrabo-Carazo; Miguel Andres-Martin; Cheng Shen; Lorenzo Minola; Jose A. Guijarro; Enric Aguilar; Manola Brunet; Richard G.J. Flay; Sergio M. Vicente-Serrano; et al. (Atmospheric Research, 2023)

Discovery and exploration of monosaccharide linked dimers of galectin-3 inhibitors to target fibrosis - Jacob J. Swidorski; Brett R. Beno; Chunjian Liu; David S. Yoon; Kaushik Ghosh; Harinath Sale; Devang Shah; Kriti Acharya; Joseph Yanchunas; Priyanka Haldar; Narasimharaju Kalidindi; Jinal K. Shukla; et al. (Medicinal Chemistry Research, 2023)

Advance toward isolation, extraction, metabolism and health benefits of kaempferol, a major dietary flavonoid with future perspectives - Li Yang; Yongchao Gao; Vivek K. Bajpai; Heba A. El-Kammar; Jesus Simal-Gandara; Hui Cao; Ka-Wing Cheng; Mingfu Wang; Randolph R. J. Arroo; Liang Zou; Mohamed A. Farag; Yonghua Zhao; et al. (Critical Reviews in Food Science and Nutrition, 2023)

High-performance aqueous zinc-ion hybrid capacitors based on 3D printed metal-organic framework cathodes - Noelle R. Catarineu; Dun Lin; Cheng Zhu; Diego I. Oyarzun; Yat Li (Chemical Engineering Journal, 2023)

Interactions between marine megafauna and plastic pollution in Southeast Asia - Lucy C.M. Omeyer; Emily M. Duncan; Neil Angelo S. Abreo; Jo Marie V. Acebes; Lea A. AngSinco-Jimenez; Sabiqah T. Anuar; Lemnuel V. Aragones; Gonzalo Araujo; Luis R. Carrasco; Marcus A.H. Chua; Muhammad R. Cordova; Lantun P. Dewanti; et al. (Science of The Total Environment, 2023)

An annually laminated stalagmite from the eastern Qinghai-Tibetan Plateau provides evidence of climate instability during the early MIS5e in the Asian summer monsoon - Tao Gao; Pingzhong Zhang; Hai Cheng; Leilei Zhang; Xinhu Li; Hongyu Shi; Wei Jia; Youfeng Ning; Hanying Li; R. Lawrence Edwards (Science China Earth Sciences, 2023)

Fluorescence Sensor for Water in Organic Solvent Using Graphene Oxide- Rhodamine B and Cucurbit[7]uril - Pavitra Rajendran; Radhakrishnan SathishKannan; Karuppasamy Karpagalakshmi; Lakshminarayanan Piramuthu; Erumaipatty R. Nagarajan; Senthilmurugan Subbiah; Cheng Yang; Narayanan Selvapalam (Journal of Fluorescence, 2023)

mTOR pathway candidate genes and obesity interaction on breast cancer risk in black women from the Women’s Circle of Health Study - Mmadili N. Ilozumba; Lusine Yaghjyan; Susmita Datta; Jinying Zhao; Chi-Chen Hong; Kathryn L. Lunetta; Gary Zirpoli; Elisa V. Bandera; Julie R. Palmer; Song Yao; Christine B. Ambrosone; Ting-Yuan David Cheng (Cancer Causes & Control, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Micro-aeration assisted with electrogenic respiration enhanced the microbial catabolism and ammonification of aromatic amines in industrial wastewater - Ke Shi; Haoyi Cheng; Carolyn R. Cornell; Haiwei Wu; Shuhong Gao; Jiandong Jiang; Tiejun Liu; Aijie Wang; Jizhong Zhou; Bin Liang (Journal of Hazardous Materials, 2023)

High altitude Pliocene to Pleistocene vegetation and climate change of the Kunlun Pass Basin, NE Tibetan Plateau - Florian Schwarz; Ulrich Salzmann; Feng Cheng; Jian Ni; Junsheng Nie; Megan R. Patchett; Xiangzhong Li; Lin Li; John Woodward; Carmala Garzione (Global and Planetary Change, 2023)

Conservation agriculture in intensive rice cropping reverses soil potassium depletion - M. J. Islam; M. Cheng; U. Kumar; M. Maniruzzaman; S. S. Nasreen; M. E. Haque; M. Jahiruddin; R. W. Bell; M. M. R. Jahangir (Nutrient Cycling in Agroecosystems, 2023)

Orbital‐ to millennial‐scale variation of the speleothem δ 18 O record during Marine Isotope Stages 5 to 3 on the southeast Chinese Loess Plateau and its climatic and environmental implications - YANJUN CAI; HAI CHENG; XING CHENG; ZHENGGUO SHI; YANBIN LU; LE MA; CARLOS PÉREZ‐MEJÍAS; HAIWEI ZHANG; YINGYING WEI; GANG XUE; HANYING LI; MEI HE; et al. (Journal of Quaternary Science, 2023)
The Chinese Loess Plateau (CLP) is located in northern China, a region climatically dominated by the East Asian monsoon. Speleothem records from this region are crucial to fully understand the variability of the East Asian summer monsoon (EASM) and reconcile the disparity seen between loess records and speleothem δ 18 O records for the EASM. Here, we present an absolutely dated stalagmite isotope record spanning most of Marine Isotope Stage (MIS) 5 to MIS 3 from Xiaotian Cave, southeast CLP. The Xiaotian speleothem δ 18 O record is dominated by precessional variations and punctuated by notable millennial‐scale oscillations; in particular, the δ 18 O values in MIS 5e, 5c and 5a were in the same range, consistent with other speleothem δ 18 O records from the EASM region within quoted errors, verifying the difference between speleothem δ 18 O and loess records (e.g. magnetic susceptibility) and the proposition that those two archives may record different aspects of the EASM changes. The similar values in MIS 5e, 5c and 5a observed from the speleothem δ 18 O records in EASM regions, incompatible with the relatively higher North Hemisphere Summer Insolation (NHSI) during MIS 5e, were probably caused by an equivalent or even increased contribution of 18 O‐enriched moisture from the South China Sea and North Pacific, implying that an El Niño‐like state existed during MIS 5e. The Xiaotian δ 18 O values increased abruptly at ~121.7 thousand years (kyr) before the present ( bp , present refers to ad 1950), consistent with the trend seen in previously reported Chinese speleothem δ 18 O records, indicating an abrupt regime shift in atmospheric circulations or hydroclimate conditions in the Asian monsoon systems. It cannot be definitely ruled out that an increase in sea ice extent in the northern North Atlantic, responding to a decrease of NHSI, reached a threshold to have led to abrupt changes in the Asian summer monsoon (ASM) through rapid shifts in the position of circulation of the westerlies and/or in the position of Intertropical Convergence Zone (ITCZ). Here, we hypothesized that sea surface cooling in the tropical Indian and Pacific Ocean caused by the decreased summer insolation reached a threshold that eventually resulted in an abrupt shift to more positive precipitation δ 18 O, either through weakened convection over the tropical ocean, or through abrupt shifts in moisture transport and cycling of tropical moisture sources for the ASM. The Xiaotian speleothem δ 18 O record also shows centennial‐scale variability with amplitude up to 3‰ within MIS 5e. These changes are similar to variations recorded by the speleothem δ 18 O record from Tianmen Cave on the south‐central Tibetan Plateau and Shangxiaofeng Cave in Shandong Province, northern China, suggesting a heightened sensitivity of precipitation δ 18 O to climate changes at the marginal zone of the ASM even during the warm and humid MIS 5e interglacial. Climatic oscillations during MIS 5e appear to be comparable to those typical of the Holocene, implying rather unstable climate conditions during the Last Interglacial.

Quantifying long‐term phenological patterns of aerial insectivores roosting in the Great Lakes region using weather surveillance radar - Yuting Deng; Maria Carolina T. D. Belotti; Wenlong Zhao; Zezhou Cheng; Gustavo Perez; Elske Tielens; Victoria F. Simons; Daniel R. Sheldon; Subhransu Maji; Jeffrey F. Kelly; Kyle G. Horton (Global Change Biology, 2023)
Organisms have been shifting their timing of life history events (phenology) in response to changes in the emergence of resources induced by climate change. Yet understanding these patterns at large scales and across long time series is often challenging. Here we used the US weather surveillance radar network to collect data on the timing of communal swallow and martin roosts and evaluate the scale of phenological shifts and its potential association with temperature. The discrete morning departures of these aggregated aerial insectivores from ground‐based roosting locations are detected by radars around sunrise. For the first time, we applied a machine learning algorithm to automatically detect and track these large‐scale behaviors. We used 21 years of data from 12 weather surveillance radar stations in the Great Lakes region to quantify the phenology in roosting behavior of aerial insectivores at three spatial levels: local roost cluster, radar station, and across the Great Lakes region. We show that their peak roosting activity timing has advanced by 2.26 days per decade at the regional scale. Similar signals of advancement were found at the station scale, but not at the local roost cluster scale. Air temperature trends in the Great Lakes region during the active roosting period were predictive of later stages of roosting phenology trends (75% and 90% passage dates). Our study represents one of the longest‐term broad‐scale phenology examinations of avian aerial insectivore species responding to environmental change and provides a stepping stone for examining potential phenological mismatches across trophic levels at broad spatial scales.

Bioactive compounds, health benefits, and industrial applications of Tartary buckwheat ( Fagopyrum tataricum ) - Liang Zou; Dingtao Wu; Guixing Ren; Yichen Hu; Lianxin Peng; Jianglin Zhao; Pascual Garcia-Perez; Maria Carpena; Miguel A. Prieto; Hui Cao; Ka-Wing Cheng; Mingfu Wang; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Natural variations of OsAUX5, a target gene of OsWRKY78, control the neutral essential amino acid content in rice grains - Yuheng Shi; Yuanyuan Zhang; Yangyang Sun; Ziyang Xie; Yu Luo; Qiyuan Long; Jiahui Feng; Xueqing Liu; Bi Wang; Dujun He; Junxia Ren; Peizhen Guo; et al. (Molecular Plant, 2023)

A parametric investigation of methane jets in direct-injection compression-ignition conditions - Quancen Wan; Guanxiong Zhai; Cheng Wang; Anthony C.Y. Yuen; Paul R. Medwell; Sanghoon Kook; Guan Heng Yeoh; Qing Nian Chan (Fuel, 2023)

Inferences of waste management policy and reduction of marine debris in Southern Taiwan - H.-T. Yang; H.-R. Chao; Y.-F. Cheng (International Journal of Environmental Science and Technology, 2023)

Linking human impacts to community processes in terrestrial and freshwater ecosystems - Ian R. McFadden; Agnieszka Sendek; Morgane Brosse; Peter M. Bach; Marco Baity‐Jesi; Janine Bolliger; Kurt Bollmann; Eckehard G. Brockerhoff; Giulia Donati; Friederike Gebert; Shyamolina Ghosh; Hsi‐Cheng Ho; et al. (Ecology Letters, 2023)
Human impacts such as habitat loss, climate change and biological invasions are radically altering biodiversity, with greater effects projected into the future. Evidence suggests human impacts may differ substantially between terrestrial and freshwater ecosystems, but the reasons for these differences are poorly understood. We propose an integrative approach to explain these differences by linking impacts to four fundamental processes that structure communities: dispersal, speciation, species‐level selection and ecological drift. Our goal is to provide process‐based insights into why human impacts, and responses to impacts, may differ across ecosystem types using a mechanistic, eco‐evolutionary comparative framework. To enable these insights, we review and synthesise (i) how the four processes influence diversity and dynamics in terrestrial versus freshwater communities, specifically whether the relative importance of each process differs among ecosystems, and (ii) the pathways by which human impacts can produce divergent responses across ecosystems, due to differences in the strength of processes among ecosystems we identify. Finally, we highlight research gaps and next steps, and discuss how this approach can provide new insights for conservation. By focusing on the processes that shape diversity in communities, we aim to mechanistically link human impacts to ongoing and future changes in ecosystems.

Nanotechnology- A ray of hope for heavy metals removal - V. Mohanapriya; R. Sakthivel; Nguyen Dang Khoa Pham; Chin Kui Cheng; Huu Son Le; Thi Minh Hao Dong (Chemosphere, 2023)

Infusing satellite data into aerosol forecast for near real-time episode detection and diagnosis in East Asia - Sheng-Po Chen; Cheng-Hsuan (Sarah) Lu; James E. Davies; Chang-Feng Ou-Yang; Neng-Huei Lin; Amy K. Huff; Bradley R. Pierce; Shobha Kondragunta; Jia-Lin Wang (Science of The Total Environment, 2023)

Variations in Asian summer monsoon and hydroclimate during Heinrich stadials 4 revealed by stalagmite stable isotopes and trace elements - Yao Wu; Ting-Yong Li; Jun-Yun Li; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Yan Yang; Jing-Yao Zhao; Chao-Jun Chen; Ming-Qiang Liang; Si-Ya Xiao; Hai-Ying Qiu; et al. (Quaternary Science Reviews, 2023)

Incorporating field-based research into remote learning: An assessment of soil lead pollution in different land-use types in Los Angeles - Wei-Cheng Hung; Naomi Adams; Zanobia R. Ibrahim-Watkins; Dorothy Nguyen; Tricia Jain; Yu-Han Wang; Jennifer A. Jay (Environmental Research, 2023)

Oxygen-enriched vacancy spinel MFe2O4/carbon (M = Ni, Mn, Co) derived from metal-organic frameworks toward boosting lithium storage - Wenqing Du; Yongqian Zheng; Xueyi Liu; Jie Cheng; R. Chenna Krishna Reddy; Akif Zeb; Xiaoming Lin; Yifan Luo (Chemical Engineering Journal, 2023)

A 10-miRNA risk score-based prediction model for pathological complete response to neoadjuvant chemotherapy in hormone receptor-positive breast cancer - Chang Gong; Ziliang Cheng; Yaping Yang; Jun Shen; Yingying Zhu; Li Ling; Wanyi Lin; Zhigang Yu; Zhihua Li; Weige Tan; Chushan Zheng; Wenbo Zheng; et al. (Science China Life Sciences, 2022)

Differentiation Epitopes Define Hematopoietic Stem Cells and Change with Cell Cycle Passage - Laura R. Goldberg; Mark S. Dooner; Elaine Papa; Mandy Pereira; Michael Del Tatto; Yan Cheng; Sicheng Wen; Peter J. Quesenberry (Stem Cell Reviews and Reports, 2022)
Hematopoietic stem cells express differentiation markers B220 and Gr1 and are proliferative. We have shown that the expression of these entities changes with cell cycle passage. Overall, we conclude that primitive hematopoietic stem cells alter their differentiation potential with cell cycle progression. Graphical Abstract Murine derived long-term hematopoietic stem cells (LT-HSC) are cycling and thus always changing phenotype. Here we show that over one half of marrow LT-HSC are in the population expressing differentiation epitopes and that B220 and Gr-1 positive populations are replete with LT-HSC after a single FACS separation but if subjected to a second separation these cells no longer contain LT-HSC. However, with second separated cells there is a population appearing that is B220 negative and replete with cycling c-Kit, Sca-1 CD150 positive LT-HSC. There is a 3–4 h interval between the first and second B220 or GR-1 FACS separation during which the stem cells continue to cycle. Thus, the LT-HSC have lost B220 or GR-1 expression as the cells progress through cell cycle, although they have maintained the c-kit, Sca-1 and CD150 stem cells markers over this time interval. These data indicate that cycling stem cells express differentiation epitopes and alter their differentiation potential with cell cycle passage.

The air mycobiome is decoupled from the soil mycobiome in the California San Joaquin Valley - Robert Wagner; Liliam Montoya; Cheng Gao; Jennifer R. Head; Justin Remais; John W. Taylor (Molecular Ecology, 2022)
Dispersal is a key force in the assembly of fungal communities and the air is the dominant route of dispersal for most fungi. Understanding the dynamics of airborne fungi is important for determining their source and for helping to prevent fungal disease. This understanding is important in the San Joaquin Valley of California, which is home to 4.2 million people and where the airborne fungus Coccidioides is responsible for the most important fungal disease of otherwise healthy humans, coccidioidomycosis. The San Joaquin Valley is the most productive agricultural region in the United States, with the principal crops grown therein susceptible to fungal pathogens. Here, we characterize the fungal community in soil and air on undeveloped and agricultural land in the San Joaquin Valley using metabarcoding of the internal transcribed spacer 2 variable region of fungal rDNA. Using 1,002 individual samples, we report one of the most extensive studies of fungi sampled simultaneously from air and soil using modern sequencing techniques. We find that the air mycobiome in the San Joaquin Valley is distinct from the soil mycobiome, and that the assemblages of airborne fungi from sites as far apart as 160 km are far more similar to one another than to the fungal communities in nearby soils. Additionally, we present evidence that airborne fungi in the San Joaquin Valley are subject to dispersal limitation and cyclical intra‐annual patterns of community composition. Our findings are broadly applicable to understanding the dispersal of airborne fungi and the taxonomic structure of airborne fungal assemblages.

Coastal Vegetation and Bathymetry Influence Blue Crab Abundance Across Spatial Scales - Selina L. Cheng; Kinsey N. Tedford; Rachel S. Smith; Sean Hardison; Michael R. Cornish; Max C. N. Castorani (Estuaries and Coasts, 2022)
Blue crabs ( Callinectes sapidus ) are highly mobile, ecologically-important mesopredators that support multimillion-dollar fisheries along the western Atlantic Ocean. Understanding how blue crabs respond to coastal landscape change is integral to conservation and management, but such insights have been limited to a narrow range of habitats and spatial scales. We examined how local-scale to landscape-scale habitat characteristics and bathymetric features (channels and oceanic inlets) affect the relative abundance (catch per unit effort, CPUE) of adult blue crabs across a > 33 km 2 seagrass landscape in coastal Virginia, USA. We found that crab CPUE was 1.7 × higher in sparse (versus dense) seagrass, 2.4 × higher at sites farther from (versus nearer to) salt marshes, and unaffected by proximity to oyster reefs. The probability that a trapped crab was female was 5.1 × higher in sparse seagrass and 8 × higher near deep channels. The probability of a female crab being gravid was 2.8 × higher near seagrass meadow edges and 3.3 × higher near deep channels. Moreover, the likelihood of a gravid female having mature eggs was 16 × greater in sparse seagrass and 32 × greater near oceanic inlets. Overall, we discovered that adult blue crab CPUE is influenced by seagrass, salt marsh, and bathymetric features on scales from meters to kilometers, and that habitat associations depend on sex and reproductive stage. Hence, accelerating changes to coastal geomorphology and vegetation will likely alter the abundance and distribution of adult blue crabs, challenging marine spatial planning and ecosystem-based fisheries management.

Aging and white matter microstructure and macrostructure: a longitudinal multi-site diffusion MRI study of 1218 participants - Kurt G. Schilling; Derek Archer; Fang-Cheng Yeh; Francois Rheault; Leon Y. Cai; Colin Hansen; Qi Yang; Karthik Ramdass; Andrea T. Shafer; Susan M. Resnick; Kimberly R. Pechman; Katherine A. Gifford; et al. (Brain Structure and Function, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Quantifying cancer risk from exposures to medical imaging in the Risk of Pediatric and Adolescent Cancer Associated with Medical Imaging (RIC) Study: research methods and cohort profile - Marilyn L. Kwan; Diana L. Miglioretti; Erin J. A. Bowles; Sheila Weinmann; Robert T. Greenlee; Natasha K. Stout; Alanna Kulchak Rahm; Susan A. Alber; Priscila Pequeno; Lisa M. Moy; Carly Stewart; Cindy Fong; et al. (Cancer Causes & Control, 2022)

Early Last Interglacial environmental changes recorded by speleothems from Katerloch (south‐east Austria) - Charlotte Honiat; Daniela Festi; Paul S. Wilcox; R. Lawrence Edwards; Hai Cheng; Christoph Spötl (Journal of Quaternary Science, 2022)
In the European Alps, the Last Interglacial (LIG, ~129–116 ka) has been primarily studied using pollen preserved in mires and lake sediments. These records document the vegetation succession across the LIG, but are poorly constrained chronologically. Here, we present a precisely dated stable isotope record for the early LIG (129.6 ± 0.4 to 125.0 ± 0.8 ka) based on two stalagmites from Katerloch, a cave located on the south‐eastern side of the Alps. The onset of the interglacial is marked by a sharp rise in the oxygen isotope values at 129.4 ± 0.4 ka, consistent within dating uncertainty with the timing of Termination II as recorded by other Alpine speleothems. Carbon isotope values show an equally prominent drop at Termination II and the establishment of a forest ecosystem. Although concentrations are low, pollen from these stalagmites provide insights into how the local vegetation changed across the first five millennia of the LIG. The spectra indicate a vegetation optimum recorded by the occurrence of warm‐demanding taxa typical of the Eemian mesocratic phase. By combining stable isotopes and pollen data, we propose an absolutely dated chronological framework for peri‐Alpine pollen successions from lacustrine sediments covering the first half of the LIG.

Two heads are better than one: current landscape of integrating QSP and machine learning - Tongli Zhang; Ioannis P. Androulakis; Peter Bonate; Limei Cheng; Tomáš Helikar; Jaimit Parikh; Christopher Rackauckas; Kalyanasundaram Subramanian; Carolyn R. Cho; Ioannis P. Androulakis; Peter Bonate; Ivan Borisov; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2022)
Quantitative systems pharmacology (QSP) modeling is applied to address essential questions in drug development, such as the mechanism of action of a therapeutic agent and the progression of disease. Meanwhile, machine learning (ML) approaches also contribute to answering these questions via the analysis of multi-layer ‘omics’ data such as gene expression, proteomics, metabolomics, and high-throughput imaging. Furthermore, ML approaches can also be applied to aspects of QSP modeling. Both approaches are powerful tools and there is considerable interest in integrating QSP modeling and ML. So far, a few successful implementations have been carried out from which we have learned about how each approach can overcome unique limitations of the other. The QSP + ML working group of the International Society of Pharmacometrics QSP Special Interest Group was convened in September, 2019 to identify and begin realizing new opportunities in QSP and ML integration. The working group, which comprises 21 members representing 18 academic and industry organizations, has identified four categories of current research activity which will be described herein together with case studies of applications to drug development decision making. The working group also concluded that the integration of QSP and ML is still in its early stages of moving from evaluating available technical tools to building case studies. This paper reports on this fast-moving field and serves as a foundation for future codification of best practices.

Increasing the spatial and temporal impact of ecological research: A roadmap for integrating a novel terrestrial process into an Earth system model - Emily Kyker‐Snowman; Danica L. Lombardozzi; Gordon B. Bonan; Susan J. Cheng; Jeffrey S. Dukes; Serita D. Frey; Elin M. Jacobs; Risa McNellis; Joshua M. Rady; Nicholas G. Smith; R. Quinn Thomas; William R. Wieder; et al. (Global Change Biology, 2022)
Terrestrial ecosystems regulate Earth's climate through water, energy, and biogeochemical transformations. Despite a key role in regulating the Earth system, terrestrial ecology has historically been underrepresented in the Earth system models (ESMs) that are used to understand and project global environmental change. Ecology and Earth system modeling must be integrated for scientists to fully comprehend the role of ecological systems in driving and responding to global change. Ecological insights can improve ESM realism and reduce process uncertainty, while ESMs offer ecologists an opportunity to broadly test ecological theory and increase the impact of their work by scaling concepts through time and space. Despite this mutualism, meaningfully integrating the two remains a persistent challenge, in part because of logistical obstacles in translating processes into mathematical formulas and identifying ways to integrate new theories and code into large, complex model structures. To help overcome this interdisciplinary challenge, we present a framework consisting of a series of interconnected stages for integrating a new ecological process or insight into an ESM. First, we highlight the multiple ways that ecological observations and modeling iteratively strengthen one another, dispelling the illusion that the ecologist's role ends with initial provision of data. Second, we show that many valuable insights, products, and theoretical developments are produced through sustained interdisciplinary collaborations between empiricists and modelers, regardless of eventual inclusion of a process in an ESM. Finally, we provide concrete actions and resources to facilitate learning and collaboration at every stage of data‐model integration. This framework will create synergies that will transform our understanding of ecology within the Earth system, ultimately improving our understanding of global environmental change, and broadening the impact of ecological research.

Plant metabolism paves the way for breeding crops with high nutritional value and stable yield - Cheng Jin; Chuanying Fang; Yuanyuan Zhang; Alisdair R. Fernie; Jie Luo (Science China Life Sciences, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Disturbance shapes the US forest governance frontier: A review and conceptual framework for understanding governance change - Courtney A. Schultz; Jesse B. Abrams; Emily Jane Davis; Antony S. Cheng; Heidi R. Huber-Stearns; Cassandra Moseley (Ambio, 2021)

Human activity and climate change triggered the expansion of rocky desertification in the karst areas of Southwestern China - Chaojun Chen; Daoxian Yuan; Hai Cheng; Tsailuen Yu; Chuanchou Shen; R. Lawrence Edwards; Yao Wu; Siya Xiao; Jian Zhang; Tao Wang; Ran Huang; Ziqi Liu; et al. (Science China Earth Sciences, 2021)

Speleothem‐based chronology and environmental context of deposits from the Mishin Kamik Cave, NW Bulgaria – A contribution to the archaeological study of the Late Pleistocene human occupation in the Balkans - Sophie Verheyden; Elena Marinova; Stefanka Ivanova; Christian Burlet; Hai Cheng; Lawrence R. Edwards; Thomas Goovaerts; Maria Gurova (Journal of Quaternary Science, 2021)
The Balkan Peninsula represents one of the most important human pathways into and out of Europe during the Pleistocene. Mishin Kamik cave, located in the karst region of Western Stara Planina, has a rich faunal content and shows promising features indicating a human occupation site with the discovery of potential bone artefacts and an intriguing accumulation of bear skulls and bones. Petrographic study and U‐series dating of a stalagmite and other calcite deposits in the cave provide an absolute chronological frame for the detrital infillings and their archaeological content and inform the environmental and climatic context of the cave evolution. Most detrital deposits in the cave were probably deposited before Marine Isotope Stage (MIS) 5 and the cave morphology and sedimentary deposits display current morphologies since ~135 ka. Consequently, the palaeontological and archaeological findings are older than ~135 ka. Calcite dated on and under the accumulation of bear skulls and bones suggests deposition during MIS 7. A first depositional contextualization of the bone accumulation does not allow us to discriminate between a natural or anthropogenic origin. The study emphasizes the added value of speleothem studies in archaeological sites and particularly in bringing a well‐constrained chronological and environmental framework.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Summer Monsoon Rainfall Variability in Central China over the Past 4700 Years and Its Possible Link to Solar Activity - Jingwei Zhang; Kan Zhao; Xinggong Kong; Yongjin Wang; Xianfang Wang; Shushuang Liu; Zhenjun Wang; Hai Cheng; R. Lawrence Edwards (Journal of Meteorological Research, 2021)

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

The influence of vector‐borne disease on human history: socio‐ecological mechanisms - Tejas S. Athni; Marta S. Shocket; Lisa I. Couper; Nicole Nova; Iain R. Caldwell; Jamie M. Caldwell; Jasmine N. Childress; Marissa L. Childs; Giulio A. De Leo; Devin G. Kirk; Andrew J. MacDonald; Kathryn Olivarius; et al. (Ecology Letters, 2021)
Vector‐borne diseases (VBDs) are embedded within complex socio‐ecological systems. While research has traditionally focused on the direct effects of VBDs on human morbidity and mortality, it is increasingly clear that their impacts are much more pervasive. VBDs are dynamically linked to feedbacks between environmental conditions, vector ecology, disease burden, and societal responses that drive transmission. As a result, VBDs have had profound influence on human history. Mechanisms include: (1) killing or debilitating large numbers of people, with demographic and population‐level impacts; (2) differentially affecting populations based on prior history of disease exposure, immunity, and resistance; (3) being weaponised to promote or justify hierarchies of power, colonialism, racism, classism and sexism; (4) catalysing changes in ideas, institutions, infrastructure, technologies and social practices in efforts to control disease outbreaks; and (5) changing human relationships with the land and environment. We use historical and archaeological evidence interpreted through an ecological lens to illustrate how VBDs have shaped society and culture, focusing on case studies from four pertinent VBDs: plague, malaria, yellow fever and trypanosomiasis. By comparing across diseases, time periods and geographies, we highlight the enormous scope and variety of mechanisms by which VBDs have influenced human history.

Response of plantain (Plantago lanceolata L.) supplementation on nutritional, endo-parasitic, and endocrine status in lambs - M. M. Reza; M. R. A. Redoy; M. A. Rahman; S. Ety; M. A. Alim; L. Cheng; M. Al-Mamun (Tropical Animal Health and Production, 2021)

Calcium sensitivity during staircase with sequential incompletely fused contractions - Lisa D. Glass; Arthur J. Cheng; Brian R. MacIntosh (Journal of Muscle Research and Cell Motility, 2021)

Winter warming rapidly increases carbon degradation capacities of fungal communities in tundra soil: Potential consequences on carbon stability - Jingmin Cheng; Yunfeng Yang; Mengting M. Yuan; Qun Gao; Liyou Wu; Ziyan Qin; Zhou J. Shi; Edward A. G. Schuur; James R. Cole; James M. Tiedje; Jizhong Zhou (Molecular Ecology, 2021)
High‐latitude tundra ecosystems are increasingly affected by climate warming. As an important fraction of soil microorganisms, fungi play essential roles in carbon degradation, especially the old, chemically recalcitrant carbon. However, it remains obscure how fungi respond to climate warming and whether fungi, in turn, affect carbon stability of tundra. In a 2‐year winter soil warming experiment of 2°C by snow fences, we investigated responses of fungal communities to warming in the active layer of an Alaskan tundra. Although fungal community composition, revealed by the 28S rRNA gene amplicon sequencing, remained unchanged ( p > .05), fungal functional gene composition, revealed by a microarray named GeoChip, was altered ( p p p

Co-designed Land-use Scenarios and their Implications for Storm Runoff and Streamflow in New England - Andrew J. Guswa; Brian Hall; Chingwen Cheng; Jonathan R. Thompson (Environmental Management, 2020)

A multiple-proxy stalagmite record reveals historical deforestation in central Shandong, northern China - Liangcheng Tan; Wen Liu; Tianli Wang; Peng Cheng; Jingjie Zang; Xiqian Wang; Le Ma; Dong Li; Jianghu Lan; R. Lawrence Edwards; Hai Cheng; Hai Xu; et al. (Science China Earth Sciences, 2020)

Introgression of perennial growth habit from Lophopyrum elongatum into wheat - Juliya Abbasi; Jiale Xu; Hamid Dehghani; Ming-Cheng Luo; Karin R. Deal; Patrick E. McGuire; Jan Dvorak (Theoretical and Applied Genetics, 2020)

PAWI-2: A novel inhibitor for eradication of cancer - Jiongjia Cheng; John R. Cashman (Medicinal Chemistry Research, 2020)

7700-year persistence of an isolated, free-living coral assemblage in the Galápagos Islands: a model for coral refugia? - J. S. Feingold; B. Riegl; K. Hendrickson; L. T. Toth; H. Cheng; R. L. Edwards; R. B. Aronson (Coral Reefs, 2020)

The combined effect of high pressure processing and dimethyl dicarbonate to inactivate foodborne pathogens in apple juice - Rodrigo R. Petrus; John J. Churey; Gerard A. Humiston; Rebecca M. Cheng; Randy W. Worobo (Brazilian Journal of Microbiology, 2020)

Jurassic uplift and erosion of the northeast Queensland continental margin: evidence from (U–Th)/He thermochronology combined with U–Pb detrital zircon age spectra - Y. Cheng; C. N. Todd; R. A. Henderson; M. Danišík; F. Sahlström; Z. Chang; I. Corral (Australian Journal of Earth Sciences, 2020)

On the PsbS-induced quenching in the plant major light-harvesting complex LHCII studied in proteoliposomes - Krzysztof Pawlak; Suman Paul; Cheng Liu; Michael Reus; Chunhong Yang; Alfred R. Holzwarth (Photosynthesis Research, 2020)

Genome-wide introgression from a bread wheat × Lophopyrum elongatum amphiploid into wheat - Jiale Xu; Le Wang; Karin R. Deal; Tingting Zhu; Ramesh K. Ramasamy; Ming-Cheng Luo; Julia Malvick; Frank M. You; Patrick E. McGuire; Jan Dvorak (Theoretical and Applied Genetics, 2020)

Effects of Electrode Diameter and Contact Material on Signal Morphology of Gastric Bioelectrical Slow Wave Recordings - Abhishek A. Kamat; Niranchan Paskaranandavadivel; Saeed Alighaleh; Leo K. Cheng; Timothy R. Angeli (Annals of Biomedical Engineering, 2020)

Consensus Paper: Experimental Neurostimulation of the Cerebellum - Lauren N. Miterko; Kenneth B. Baker; Jaclyn Beckinghausen; Lynley V. Bradnam; Michelle Y. Cheng; Jessica Cooperrider; Mahlon R. DeLong; Simona V. Gornati; Mark Hallett; Detlef H. Heck; Freek E. Hoebeek; Abbas Z. Kouzani; et al. (The Cerebellum, 2019)

Dynamic modifications of biomacromolecules: mechanism and chemical interventions - Chu Wang; Peng Zou; Caiguang Yang; Lei Liu; Liang Cheng; Xiaopeng He; Liang Zhang; Yan Zhang; Hualiang Jiang; Peng R. Chen (Science China Life Sciences, 2019)

Essential in vitro diagnostics for advanced HIV and serious fungal diseases: international experts’ consensus recommendations - Felix Bongomin; Nelesh P. Govender; Arunaloke Chakrabarti; Florence Robert-Gangneux; David R. Boulware; Afia Zafar; Rita O. Oladele; Malcolm D. Richardson; Jean-Pierre Gangneux; Ana Alastruey-Izquierdo; Joel Bazira; Tom H. Boyles; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Is Chinese stalagmite δ18O solely controlled by the Indian summer monsoon? - Dong Li; Liangcheng Tan; Yanjun Cai; Xiuyang Jiang; Le Ma; Hai Cheng; R. Lawrence Edwards; Haiwei Zhang; Yongli Gao; Zhisheng An (Climate Dynamics, 2019)

Associations between microplastic pollution and land use in urban wetland sediments - Kallie R. Townsend; Hsuan-Cheng Lu; David J. Sharley; Vincent Pettigrove (Environmental Science and Pollution Research, 2019)

An End-to-end System for Automatic Characterization of Iba1 Immunopositive Microglia in Whole Slide Imaging - Alexander D. Kyriazis; Shahriar Noroozizadeh; Amir Refaee; Woongcheol Choi; Lap-Tak Chu; Asma Bashir; Wai Hang Cheng; Rachel Zhao; Dhananjay R. Namjoshi; Septimiu E. Salcudean; Cheryl L. Wellington; Guy Nir (Neuroinformatics, 2019)

Role of a VGF/BDNF/TrkB Autoregulatory Feedback Loop in Rapid-Acting Antidepressant Efficacy - Cheng Jiang; Wei-Jye Lin; Stephen R. Salton (Journal of Molecular Neuroscience, 2019)

Mitochondrial variation in small brown planthoppers linked to multiple traits and probably reflecting a complex evolutionary trajectory - Jing‐Tao Sun; Xing‐Zhi Duan; Ary A. Hoffmann; Yan Liu; Michael R. Garvin; Lei Chen; Gao Hu; Jin‐Cheng Zhou; Hai‐Jian Huang; Xiao‐Feng Xue; Xiao‐Yue Hong (Molecular Ecology, 2019)
While it has been proposed in several taxa that the mitochondrial genome is associated with adaptive evolution to different climatic conditions, making links between mitochondrial haplotypes and organismal phenotypes remains a challenge. Mitonuclear discordance occurs in the small brown planthopper (SBPH), Laodelphax striatellus, with one mitochondrial haplogroup (HGI) more common in the cold climate region of China relative to another form (HGII) despite strong nuclear gene flow, providing a promising model to investigate climatic adaptation of mitochondrial genomes. We hypothesized that cold adaptation through HGI may be involved, and considered mitogenome evolution, population genetic analyses, and bioassays to test this hypothesis. In contrast to our hypothesis, chill‐coma recovery tests and population genetic tests of selection both pointed to HGII being involved in cold adaptation. Phylogenetic analyses revealed that HGII is nested within HGI, and has three nonsynonymous changes in ND2 , ND5 and CYTB in comparison to HGI. These molecular changes likely increased mtDNA copy number, cold tolerance and fecundity of SBPH, particularly through a function‐altering amino acid change involving M114T in ND2 . Nuclear background also influenced fecundity and chill recovery (i.e., mitonuclear epistasis) and protein modelling indicates possible nuclear interactions for the two nonsynonymous changes in ND2 and CYTB . The high occurrence frequency of HGI in the cold climate region of China remains unexplained, but several possible reasons are discussed. Overall, our study points to a link between mtDNA variation and organismal‐level evolution and suggests a possible role of mitonuclear interactions in maintaining mtDNA diversity.

Application of Avaatech X-ray fluorescence core-scanning in Sr/Ca analysis of speleothems - Dong Li; Liangcheng Tan; Fei Guo; Yanjun Cai; Youbin Sun; Gang Xue; Xing Cheng; Hong Yan; Hai Cheng; R. Lawrence Edwards; Yongli Gao; Jessica Kelley (Science China Earth Sciences, 2019)

First detection and isolation of infectious haematopoietic necrosis virus from farmed rainbow trout in Nyeri County, Kenya - Isaac R. Mulei; Phillip N. Nyaga; Paul G. Mbuthia; Robert M. Waruiru; Cheng Xu; Øystein Evensen; Stephen Mutoloki (Journal of Fish Diseases, 2019)
Infectious haematopoietic necrosis virus (IHNV) is the causative agent of infectious haematopoietic necrosis, a disease of salmonid responsible for great economic losses. The disease occurs in most parts of the world where rainbow trout is reared but has not been previously reported in Kenya. In this study, rainbow trout fry and growers from two farms in Nyeri County were screened for IHNV. Whole fry ( n = 4 from each farm) and kidney samples from growers ( n = 15 and n = 6 from the two farms, respectively) were collected and preserved for cell culture examination or PCR analysis. Screening of samples was done by PCR followed by sequencing of the glycoprotein gene of the virus. Demonstration of the virus was done by propagation in EPC cells followed by the indirect fluorescence antibody test (IFAT). The results revealed the presence of IHNV at low prevalence of 0.1 and 0.4 for the two farms. The virus was confirmed both by IFAT and by partial sequencing of the G gene. Phylogenetic analysis revealed that the Kenyan isolates were identical to those of the J genogroup found mostly in Asia. The findings have implications for biosecurity measures and import regulations for the Kenyan rainbow trout industry.

Long-term seasonal forecasting of a major migrant insect pest: the brown planthopper in the Lower Yangtze River Valley - Gao Hu; Ming-Hong Lu; Don R. Reynolds; Hai-Kou Wang; Xiao Chen; Wan-Cai Liu; Feng Zhu; Xiang-Wen Wu; Feng Xia; Miao-Chang Xie; Xia-Nian Cheng; Ka-Sing Lim; et al. (Journal of Pest Science, 2019)

Reconstructing the western boundary variability of the Western Pacific Subtropical High over the past 200 years via Chinese cave oxygen isotope records - Jingyao Zhao; Hai Cheng; Yan Yang; Liangcheng Tan; Christoph Spötl; Youfeng Ning; Haiwei Zhang; Xing Cheng; Zhe Sun; Xianglei Li; Hanying Li; Wen Liu; et al. (Climate Dynamics, 2019)

No detection of CD4-independent human immunodeficiency virus 1 envelope glycoproteins in brain tissue of patients with or without neurological complications - Briana Quitadamo; Paul J. Peters; Matthew Koch; Katherine Luzuriaga; Cecilia Cheng-Mayer; Paul R. Clapham; Maria Paz Gonzalez-Perez (Archives of Virology, 2019)

Reassessment of the evolution of wheat chromosomes 4A, 5A, and 7B - Jan Dvorak; Le Wang; Tingting Zhu; Chad M. Jorgensen; Ming-Cheng Luo; Karin R. Deal; Yong Q. Gu; Bikram S. Gill; Assaf Distelfeld; Katrien M. Devos; Peng Qi; Patrick E. McGuire (Theoretical and Applied Genetics, 2018)

Tropical Indian Ocean warming contributions to China winter climate trends since 1960 - Qigang Wu; Yonghong Yao; Shizuo Liu; DanDan Cao; Luyao Cheng; Haibo Hu; Leng Sun; Ying Yao; Zhiqi Yang; Xuxu Gao; Steven R. Schroeder (Climate Dynamics, 2018)

High‐resolution reconstruction of 8.2‐ka BP event documented in Père Noël cave, southern Belgium - M. Allan; N. Fagel; H. J. L. van der Lubbe; H. B. Vonhof; H. Cheng; R. Lawrence Edwards; S. Verheyden (Journal of Quaternary Science, 2018)
A distinct shift in δ 18 O, δ 13 C and trace element contents of the Père Noël (PN) stalagmite from southern Belgium revealed an abrupt climatic anomaly at 8.13 ± 0.03 ka BP (before present = before 1950 AD). This anomaly is characterized by a maximum drop in the δ 18 O (−1.4‰ compared the mean) between 8.13 and 8.10 ka BP (±0.03). This drop of δ 18 O coincides with a decrease in δ 13 C and trace element (Sr, Ba and Mg) concentrations suggesting drier conditions. Our precise chronology provides the timing of the outburst of proglacial lakes Agassiz and Ojibway that caused the δ 18 O, δ 13 C and trace elemental anomalies at 8.13–8.10 ± 0.03 ka BP, which corresponds to the 8.2‐ka BP event. The PN stalagmite bears δ 18 O values in fluid inclusions that covary with the δ 18 O values in calcite, suggesting that the speleothem calcite δ 18 O primarily reflects variations in the rainfall δ 18 O. Comparison of the PN record with different marine and terrestrial archives during the 8.2‐ka BP event shows a good agreement in timing and duration, suggesting that the PN speleothem can be regarded as a valuable proxy to better understand the 8.2‐ka BP event.

Role of Ca2+ in changing active force during intermittent submaximal stimulation in intact, single mouse muscle fibers - Lisa D. Glass; Arthur J. Cheng; Brian R. MacIntosh (Pflügers Archiv - European Journal of Physiology, 2018)

Comparative Hair Trace Element Profile in the Population of Sakhalin and Taiwan Pacific Islands - Anatoly V. Skalny; Margarita G. Skalnaya; Eugeny P. Serebryansky; Irina V. Zhegalova; Andrei R. Grabeklis; Oxana A. Skalnaya; Anastasia A. Skalnaya; Pai-Tsang Huang; Cheng-Chi Wu; Anatoly T. Bykov; Alexey A. Tinkov (Biological Trace Element Research, 2018)

Using machine learning to advance synthesis and use of conservation and environmental evidence - S.H. Cheng; C. Augustin; A. Bethel; D. Gill; S. Anzaroot; J. Brun; B. DeWilde; R.C. Minnich; R. Garside; Y.J. Masuda; D.C. Miller; D. Wilkie; et al. (Conservation Biology, 2018)
Article impact statement : Machine learning optimizes processes of systematic evidence synthesis and improves its utility for evidence‐based conservation.

Responses of aquatic communities to physical and chemical parameters in agriculturally impacted coastal river systems - C. R. Petersen; N. Z. Jovanovic; M. C. Grenfell; P. J. Oberholster; P. Cheng (Hydrobiologia, 2018)

The coronafacoyl phytotoxins: structure, biosynthesis, regulation and biological activities - Dawn R. D. Bignell; Zhenlong Cheng; Luke Bown (Antonie van Leeuwenhoek, 2018)

Clinical variation in the use of echocardiography in Staphylococcus aureus bacteraemia: a multi-centre cohort study - George S. Heriot; Steven Y. C. Tong; Allen C. Cheng; Irani Thevarajan; Michele R. Levinson; Kumar Visvanathan; Danny Liew (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Novel vagrant records and occurrence of vector-borne pathogens in King Penguins (Aptenodytes patagonicus) in South Africa - Nola J. Parsons; Tertius A. Gous; Michael R. Cranfield; Lily I. Cheng; Albert Schultz; Elizabeth Horne; Robert P. Last; François Lampen; Katrin Ludynia; Barry Bousfield; Venessa Strauss; Michael A. Peirce; et al. (Polar Biology, 2018)

Characterizing the neighborhood obesogenic environment in the Multiethnic Cohort: a multi-level infrastructure for cancer health disparities research - Shannon M. Conroy; Salma Shariff-Marco; Juan Yang; Andrew Hertz; Myles Cockburn; Yurii B. Shvetsov; Christina A. Clarke; Cheryl L. Abright; Christopher A. Haiman; Loïc Le Marchand; Laurence N. Kolonel; Kristine R. Monroe; et al. (Cancer Causes & Control, 2018)

Greenhouse gases abatement by catalytic dry reforming of methane to syngas over samarium oxide-supported cobalt catalyst - B. V. Ayodele; M. R. Khan; C. K. Cheng (International Journal of Environmental Science and Technology, 2017)

A methodological approach for the design of sustainability initiatives: in pursuit of sustainable transition in China - Nasrin R. Khalili; Weiquan Cheng; Abagail McWilliams (Sustainability Science, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Molecular characterization of two Rhesus glycoproteins from the euryhaline freshwater white-rimmed stingray, Himantura signifer, and changes in their transcript levels and protein abundance in the gills, kidney, and liver during brackish water acclimation - Cheng T. Yeam; You R. Chng; Jasmine L. Y. Ong; Wai P. Wong; Shit F. Chew; Yuen K. Ip (Journal of Comparative Physiology B, 2017)

Cell Mechanosensors and the Possibilities of Using Magnetic Nanoparticles to Study Them and to Modify Cell Fate - Yajing Shen; Yu Cheng; Taro Q. P. Uyeda; Gustavo R. Plaza (Annals of Biomedical Engineering, 2017)

Evaluation of onion (Allium cepa) germplasm entries for resistance to onion thrips, Thrips tabaci (Lindeman) in Tanzania - Gabriel Michael Njau; Agnes M. S. Nyomora; Fekadu Fufa Dinssa; Jian-Cheng Chang; P. Malini; S. Subramanian; R. Srinivasan (International Journal of Tropical Insect Science, 2017)

Genetic mapping and haplotype analysis of a locus for quantitative resistance to Fusarium graminearum in soybean accession PI 567516C - Peng Cheng; Cassidy R. Gedling; Gunvant Patil; Tri D. Vuong; J. Grover Shannon; Anne E. Dorrance; Henry T. Nguyen (Theoretical and Applied Genetics, 2017)

Modelling and optimization of syngas production by methane dry reforming over samarium oxide supported cobalt catalyst: response surface methodology and artificial neural networks approach - Bamidele V. Ayodele; Maksudur R. Khan; Safdar Sk Nooruddin; Chin Kui Cheng (Clean Technologies and Environmental Policy, 2017)

Dalbavancin reduces biofilms of methicillin-resistant Staphylococcus aureus (MRSA) and methicillin-resistant Staphylococcus epidermidis (MRSE) - D. Knafl; S. Tobudic; S. C. Cheng; D. R. Bellamy; F. Thalhammer (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Greenhouse gases mitigation by CO2 reforming of methane to hydrogen-rich syngas using praseodymium oxide supported cobalt catalyst - Bamidele V. Ayodele; Maksudur R. Khan; Chin Kui Cheng (Clean Technologies and Environmental Policy, 2017)

Decreasing monsoon precipitation in southwest China during the last 240 years associated with the warming of tropical ocean - Liangcheng Tan; Yanjun Cai; Zhisheng An; Hai Cheng; Chuan-Chou Shen; Yongli Gao; R. Lawrence Edwards (Climate Dynamics, 2017)

Pathogen dynamics during invasion and establishment of white‐nose syndrome explain mechanisms of host persistence - Winifred F. Frick; Tina L. Cheng; Kate E. Langwig; Joseph R. Hoyt; Amanda F. Janicki; Katy L. Parise; Jeffrey T. Foster; A. Marm Kilpatrick (Ecology, 2017)
Disease dynamics during pathogen invasion and establishment determine the impacts of disease on host populations and determine the mechanisms of host persistence. Temporal progression of prevalence and infection intensity illustrate whether tolerance, resistance, reduced transmission, or demographic compensation allow initially declining populations to persist. We measured infection dynamics of the fungal pathogen Pseudogymnoascus destructans that causes white‐nose syndrome in bats by estimating pathogen prevalence and load in seven bat species at 167 hibernacula over a decade as the pathogen invaded, became established, and some host populations stabilized. Fungal loads increased rapidly and prevalence rose to nearly 100% at most sites within 2 yr of invasion in six of seven species. Prevalence and loads did not decline over time despite huge reductions in colony sizes, likely due to an extensive environmental reservoir. However, there was substantial variation in fungal load among sites with persisting colonies, suggesting that both tolerance and resistance developed at different sites in the same species. In contrast, one species disappeared from hibernacula within 3 yr of pathogen invasion. Variable host responses to pathogen invasion require different management strategies to prevent disease‐induced extinction and to facilitate evolution of tolerance or resistance in persisting populations.

Characterizing urban soils in New York City: profile properties and bacterial communities - Hermine Huot; Jessica Joyner; Alonso Córdoba; Richard K. Shaw; Michael A. Wilson; Roxanne Walker; Theodore R. Muth; Zhongqi Cheng (Journal of Soils and Sediments, 2017)

Diversity and biogeography of larval and juvenile notothenioid fishes in McMurdo Sound, Antarctica - Katherine R. Murphy; Elizabeth A. Kalmanek; C.-H. Christina Cheng (Polar Biology, 2017)

bFGF Protects Against Blood-Brain Barrier Damage Through Junction Protein Regulation via PI3K-Akt-Rac1 Pathway Following Traumatic Brain Injury - Zhou-Guang Wang; Yi Cheng; Xi-Chong Yu; Li-Bing Ye; Qing-Hai Xia; Noah R. Johnson; Xiaojie Wei; Da-Qing Chen; Guodong Cao; Xiao-Bing Fu; Xiao-Kun Li; Hong-Yu Zhang; et al. (Molecular Neurobiology, 2016)

West African monsoon decadal variability and surface-related forcings: second West African Monsoon Modeling and Evaluation Project Experiment (WAMME II) - Yongkang Xue; Fernando De Sales; William K.-M. Lau; Aaron Boone; Kyu-Myong Kim; Carlos R. Mechoso; Guiling Wang; Fred Kucharski; Kathleen Schiro; Masahiro Hosaka; Suosuo Li; Leonard M. Druyan; et al. (Climate Dynamics, 2016)

Characterizing barley seed macro- and micro-nutrients under multiple environmental conditions - W.T. Xue; A. Gianinetti; R. Wang; Z.J. Zhan; J. Yan; Y. Jiang; T. Fahima; G. Zhao; J.P. Cheng (Cereal Research Communications, 2016)

Does Concurrent Use of Some Botanicals Interfere with Treatment of Tuberculosis? - William R. Folk; Aaron Smith; Hailong Song; Dennis Chuang; Jianlin Cheng; Zezong Gu; Grace Sun (NeuroMolecular Medicine, 2016)

Genetic variants in the mTOR pathway and interaction with body size and weight gain on breast cancer risk in African-American and European American women - Ting-Yuan David Cheng; Jyoti Shankar; Gary Zirpoli; Michelle R. Roberts; Chi-Chen Hong; Elisa V. Bandera; Christine B. Ambrosone; Song Yao (Cancer Causes & Control, 2016)

Toxicity and in vitro activity of HIV-1 latency-reversing agents in primary CNS cells - Lachlan R. Gray; Hung On; Emma Roberts; Hao K. Lu; Michael A. Moso; Jacqueline A. Raison; Catherine Papaioannou; Wan-Jung Cheng; Anne M. Ellett; Jonathan C. Jacobson; Damian F. J. Purcell; Steve L. Wesselingh; et al. (Journal of NeuroVirology, 2016)

Sustainability from a Chinese cultural perspective: the implications of harmonious development in environmental management - Ying Li; Hao Cheng; R. J. S. Beeton; Thomas Sigler; Anthony Halog (Environment, Development and Sustainability, 2016)

Air pollution influences on exhaled nitric oxide among people with type II diabetes - Cheng Peng; Heike Luttmann-Gibson; Antonella Zanobetti; Allison Cohen; Celine De Souza; Brent A. Coull; Edward S. Horton; Joel Schwartz; Petros Koutrakis; Diane R. Gold (Air Quality, Atmosphere & Health, 2016)

Validation of self-reported comorbidity status of breast cancer patients with medical records: the California Breast Cancer Survivorship Consortium (CBCSC) - Cheryl Vigen; Marilyn L. Kwan; Esther M. John; Scarlett Lin Gomez; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2016)

Mechanical Interaction of an Expanding Coiled Stent with a Plaque-Containing Arterial Wall: A Finite Element Analysis - Tré R. Welch; Robert C. Eberhart; Subhash Banerjee; Cheng-Jen Chuong (Cardiovascular Engineering and Technology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Simultaneous refolding of denatured PsbS and reconstitution with LHCII into liposomes of thylakoid lipids - Cheng Liu; Zhimin Gao; Kun Liu; Ruixue Sun; Chunbo Cui; Alfred R. Holzwarth; Chunhong Yang (Photosynthesis Research, 2016)

Intranasal Delivery of Granulocyte Colony-Stimulating Factor Enhances Its Neuroprotective Effects Against Ischemic Brain Injury in Rats - Bao-liang Sun; Mei-qing He; Xiang-yu Han; Jing-yi Sun; Ming-feng Yang; Hui Yuan; Cun-dong Fan; Shuai Zhang; Lei-lei Mao; Da-wei Li; Zong-yong Zhang; Cheng-bi Zheng; et al. (Molecular Neurobiology, 2016)

The Earliest Gulp-Feeding Mysticete (Cetacea: Mysticeti) from the Oligocene of New Zealand - Cheng-Hsiu Tsai; R. Ewan Fordyce (Journal of Mammalian Evolution, 2015)

Photocatalytic-Fenton Degradation of Glycerol Solution over Visible Light-Responsive CuFe2O4 - Chin Kui Cheng; Zi Ying Kong; Maksudur R. Khan (Water, Air, & Soil Pollution, 2015)

Global diversity and taxonomy of the Auricularia auricula-judae complex (Auriculariales, Basidiomycota) - Fang Wu; Yuan Yuan; Shuang-Hui He; Asanka R. Bandara; Kevin D. Hyde; Vera F. Malysheva; De-Wei Li; Yu-Cheng Dai (Mycological Progress, 2015)

Racial/ethnic differences in lifestyle-related factors and prostate cancer risk: the Multiethnic Cohort Study - Song-Yi Park; Christopher A. Haiman; Iona Cheng; Sungshim Lani Park; Lynne R. Wilkens; Laurence N. Kolonel; Loïc Le Marchand; Brian E. Henderson (Cancer Causes & Control, 2015)

Global representation of tropical cyclone-induced short-term ocean thermal changes using Argo data - L. Cheng; J. Zhu; R. L. Sriver (Ocean Science, 2015)
Argo floats are used to examine tropical cyclone (TC) induced ocean thermal changes on the global scale by comparing temperature profiles before and after TC passage. We present a footprint method that analyzes cross-track thermal responses along all storm tracks during the period 2004–2012. We combine the results into composite representations of the vertical structure of the average thermal response for two different categories: tropical storms/tropical depressions (TS/TD) and hurricanes. The two footprint composites are functions of three variables: cross-track distance, water depth and time relative to TC passage. We find that this footprint strategy captures the major features of the upper-ocean thermal response to TCs on timescales up to 20 days when compared against previous case study results using in situ measurements. On the global scale, TCs are responsible for 1.87 PW (11.05 W m−2) of heat transfer annually from the global ocean to the atmosphere during storm passage (0–3 days). Of this total, 1.05 ± 0.20 PW (4.80 ± 0.85 W m−2) is caused by TS/TD and 0.82 ± 0.21 PW (6.25 ± 1.5 W m−2) is caused by hurricanes. Our findings indicate that ocean heat loss by TCs may be a substantial missing piece of the global ocean heat budget. Changes in ocean heat content (OHC) after storm passage are estimated by analyzing the temperature anomalies during wake recovery following storm events (4–20 days after storm passage) relative to pre-storm conditions. Results indicate the global ocean experiences a 0.75 ± 0.25 PW (5.98 ± 2.1 W m−2) heat gain annually for hurricanes. In contrast, under TS/TD conditions, the ocean experiences 0.41 ± 0.21 PW (1.90 ± 0.96 W m−2) ocean heat loss, suggesting the overall oceanic thermal response is particularly sensitive to the intensity of the event. The ocean heat uptake caused by all storms during the restorative stage is 0.34 PW.

Potential effects of dam cascade on fish: lessons from the Yangtze River - Fei Cheng; Wei Li; Leandro Castello; Brian R. Murphy; Songguang Xie (Reviews in Fish Biology and Fisheries, 2015)

Population genetic structure and its implication for conservation of Coreius guichenoti in the upper Yangtze River - Fei Cheng; Wei Li; Michelle Klopfer; Brian R. Murphy; Songguang Xie (Environmental Biology of Fishes, 2015)

A stepwise-cluster forecasting approach for monthly streamflows based on climate teleconnections - Y. R. Fan; W. Huang; G. H. Huang; Z. Li; Y. P. Li; X. Q. Wang; G. H. Cheng; L. Jin (Stochastic Environmental Research and Risk Assessment, 2015)

A comparison of paediatric and adult infectious diseases consultations in Australia and New Zealand - C. C. Blyth; T. Walls; A. C. Cheng; R. J. Murray; D. A. Fisher; P. R. Ingram; J. S. Davis (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Hearing abilities and sound reception of broadband sounds in an adult Risso’s dolphin (Grampus griseus) - T. Aran Mooney; Wei-Cheng Yang; Hsin-Yi Yu; Darlene R. Ketten; I-Fan Jen (Journal of Comparative Physiology A, 2015)

Recent climate warming favours more specialized cladoceran taxa in western Canadian Arctic lakes - Joshua R. Thienpont; Jennifer B. Korosi; Elisa S. Cheng; Kayla Deasley; Michael F. J. Pisaric; John P. Smol (Journal of Biogeography, 2015)
Aim Shifts in the distribution of freshwater algal communities as a result of climate‐related limnological changes are well documented; however, impacts on higher trophic levels have received less attention. For example, little is known about how Cladocera (Crustacea, Branchiopoda), often dominant invertebrates and key ecological indicators, have responded to recent warming on broad spatial and temporal scales. Here, we use lake sediment records to test the hypothesis that recent, intensive warming in the western Canadian Arctic has resulted in consistent shifts in the composition of cladoceran assemblages. Location Small, first‐order lakes in the Mackenzie Delta region of the western Canadian Arctic. Methods Sediment cores representing the recent past (approximately 150–200 years) were obtained from five lakes spanning a strong climatic gradient. Subfossil remains of Cladocera were identified and enumerated and overall primary production was inferred using spectroscopic techniques. The habitat preferences and feeding strategy of each taxon were compared. Detrended canonical correspondence analysis was used to estimate compositional turnover since 1850, and compared with that of three cladoceran assemblages from Nova Scotia, to place high‐latitude changes in context. Results Cladoceran assemblage changes occurred coincident with the timing of known regional warming and were strongly linked to estimated changes in primary production. In the northern and deepest lakes, an increase in the planktonic, filter‐feeding taxon Bosmina spp. coincided with a decrease in the generalist littoral taxa Chydorus cf. brevilabris and Alona circumfimbriata . In the more southern lakes, an increase in macrophyte‐associated scrapers Acroperus harpae and Eurycercus spp. occurred concurrently with decreases in generalist taxa. In one lake, an increase in another specialist, an obligate mud‐dwelling taxon, was observed. Main conclusions In the western Canadian Arctic, warming has resulted in an increase in cladoceran taxa occupying more specialized feeding and habitat niches. Generalist taxa capable of occupying multiple habitats and employing diverse feeding strategies have been systematically replaced by more specialist species. This response is analogous to what has been inferred for algal communities across the Northern Hemisphere, and represents the first evidence of consistent cladoceran changes to recent climate warming in high‐latitude regions.

Containment of Clostridium difficile infection without reduction in antimicrobial use in Hong Kong - V. C. C. Cheng; P. H. Chau; S. Y. C. So; J. H. K. Chen; R. W. S. Poon; S. C. Y. Wong; I. F. N. Hung; W. M. Lee; J. W. M. Tai; P. L. Ho; W. C. Yam; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Reproductive consequences of the timing of seasonal movements in a nonmigratory wild bird population - Eleni Matechou; San Chye Cheng; Lindall R. Kidd; Colin J. Garroway (Ecology, 2015)
Animal movement patterns, whether related to dispersal, migration, or ranging behaviors, vary in time. Individual movements reflect the outcomes of interactions between an individual's condition and a multitude of underlying ecological processes. Theory predicts that when competition for breeding territories is high, individuals should arrive at breeding sites earlier than what would otherwise be optimal for breeding in the absence of competition. This is because priority at a site can confer significant competitive advantages leading to better breeding outcomes. Empirical data from long‐distance migrants support this theory. However, it has not been tested within the context of fine‐scale movements in nonmigratory populations. We assessed the effect of arrival time at a breeding site on reproductive outcomes in an intensively monitored resident population of Great Tits ( Parus major ). The population was monitored passively, via passive integrated transponder (PIT) tag loggers, and actively, via catching, during breeding and nonbreeding seasons. We developed new capture–recapture–resight models that use both data types to model breeding outcome conditional on the unknown individual arrival times. In accordance with theory, individuals arrived at the woods synchronously in waves that were large at the beginning of the nonbreeding season and small toward the end, with very few arrivals in the intervening period. There was a strong effect of arrival time on the probability of breeding; the earlier an individual arrived, the more likely it was to successfully establish a nest that reached the incubation period. However, once nests were established, they had equal probabilities of failing early, regardless of arrival time. Finally, there was moderate evidence of a negative effect of arrival time on the probability of successfully fledging nestlings. These empirical findings are consistent with theoretical models that suggest an important role for competition in shaping fine‐scale seasonal movements. Our capture–recapture–resight models are extensible and suitable for a variety of applications, particularly when the goal is to estimate the effects of unobservable arrival times on subsequent ecological outcomes.

Online monitoring of the nanoscale zero-valent iron process for trichloroethylene wastewater treatment - R.-F. Yu; F.-H. Chi; W.-P. Cheng; M.-H. Wang (International Journal of Environmental Science and Technology, 2015)

The RIG-I-like helicase receptor MDA5 (IFIH1) is involved in the host defense against Candida infections - M. Jaeger; R. van der Lee; S.-C. Cheng; M. D. Johnson; V. Kumar; A. Ng; T. S. Plantinga; S. P. Smeekens; M. Oosting; X. Wang; W. Barchet; K. Fitzgerald; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Testing the mutant selection window hypothesis in vitro and in vivo with Staphylococcus aureus exposed to fosfomycin - Q. Mei; Y. Ye; Y.-L. Zhu; J. Cheng; X. Chang; Y.-Y. Liu; H.-R. Li; J.-B. Li (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Control of hospital endemicity of multiple-drug-resistant Acinetobacter baumannii ST457 with directly observed hand hygiene - V. C. C. Cheng; J. H. K. Chen; R. W. S. Poon; W. M. Lee; S. Y. C. So; S. C. Y. Wong; P. H. Chau; C. C. Y. Yip; S. S. Y. Wong; J. F. W. Chan; I. F. N. Hung; P. L. Ho; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2015)

Preclinical Pharmacokinetic/Pharmacodynamic Modeling and Simulation in the Pharmaceutical Industry: An IQ Consortium Survey Examining the Current Landscape - Edgar Schuck; Tonika Bohnert; Arijit Chakravarty; Valeriu Damian-Iordache; Christopher Gibson; Cheng-Pang Hsu; Tycho Heimbach; Anu Shilpa Krishnatry; Bianca M Liederer; Jing Lin; Tristan Maurer; Jerome T Mettetal; et al. (The AAPS Journal, 2015)

Genome-wide association study for refractive astigmatism reveals genetic co-determination with spherical equivalent refractive error: the CREAM consortium - Qing Li; Robert Wojciechowski; Claire L. Simpson; Pirro G. Hysi; Virginie J. M. Verhoeven; Mohammad Kamran Ikram; René Höhn; Veronique Vitart; Alex W. Hewitt; Konrad Oexle; Kari-Matti Mäkelä; Stuart MacGregor; et al. (Human Genetics, 2015)

Anisotropic Analysis of I-Walls in New Orleans - Sudarshan Adhikari; Chung R. Song; Alexander H.-D. Cheng (Marine Georesources & Geotechnology, 2015)

Erratum to: On-line evaluating the SS removals for chemical coagulation using digital image analysis and artificial neural networks - R.-F. Yu; W. Wang; W.-P. Cheng; M.-M. Chen (International Journal of Environmental Science and Technology, 2015)

Phytoestrogens as natural prodrugs in cancer prevention: towards a mechanistic model - Randolph R. J. Arroo; Kenneth Beresford; Avninder S. Bhambra; Mike Boarder; Roberta Budriesi; Zhong Cheng; Matteo Micucci; Ketan C. Ruparelia; Somchaiya Surichan; Vasilis P. Androutsopoulos (Phytochemistry Reviews, 2014)

Ornamental Marine Species Culture in the Coral Triangle: Seahorse Demonstration Project in the Spermonde Islands, Sulawesi, Indonesia - Susan L. Williams; Noel Janetski; Jessica Abbott; Sven Blankenhorn; Brian Cheng; R. Eliot Crafton; Sarah O. Hameed; Saipul Rapi; Dale Trockel (Environmental Management, 2014)

Structural integrity affects nitrogen removal activity of granules in semi-continuous reactors - Cesar R. Mota; Melanie A. Head; Jon C. Williams; Lucy Eland; Jay J. Cheng; Francis L. de los Reyes (Biodegradation, 2014)

Molecular mapping of genes Yr64 and Yr65 for stripe rust resistance in hexaploid derivatives of durum wheat accessions PI 331260 and PI 480016 - P. Cheng; L. S. Xu; M. N. Wang; D. R. See; X. M. Chen (Theoretical and Applied Genetics, 2014)

Juvenile morphology in baleen whale phylogeny - Cheng-Hsiu Tsai; R. Ewan Fordyce (The Science of Nature, 2014)

Influence of Thermal Annealing on the Mechanical Properties of PLLA Coiled Stents - Tré R. Welch; Robert C. Eberhart; Joan Reisch; Cheng-Jen Chuong (Cardiovascular Engineering and Technology, 2014)

Disparate Heterochronic Processes in Baleen Whale Evolution - Cheng-Hsiu Tsai; R. Ewan Fordyce (Evolutionary Biology, 2014)

Sagittal otolith microstructure, early growth and development of Coilia ectenes in the Yangtze Estuary, China - Yanfei Huang; Fei Cheng; Brian R. Murphy; Songguang Xie (Fisheries Science, 2014)

Cryptic ecology among host generalist Campylobacter jejuni in domestic animals - Samuel K. Sheppard; Lu Cheng; Guillaume Méric; Caroline P. A. de Haan; Ann‐Katrin Llarena; Pekka Marttinen; Ana Vidal; Anne Ridley; Felicity Clifton‐Hadley; Thomas R. Connor; Norval J. C. Strachan; Ken Forbes; et al. (Molecular Ecology, 2014)
Homologous recombination between bacterial strains is theoretically capable of preventing the separation of daughter clusters, and producing cohesive clouds of genotypes in sequence space. However, numerous barriers to recombination are known. Barriers may be essential such as adaptive incompatibility, or ecological, which is associated with the opportunities for recombination in the natural habitat. Campylobacter jejuni is a gut colonizer of numerous animal species and a major human enteric pathogen. We demonstrate that the two major generalist lineages of C. jejuni do not show evidence of recombination with each other in nature, despite having a high degree of host niche overlap and recombining extensively with specialist lineages. However, transformation experiments show that the generalist lineages readily recombine with one another in vitro. This suggests ecological rather than essential barriers to recombination, caused by a cryptic niche structure within the hosts.

Effects of Androgens on Early Post-ischemic Neurogenesis in Mice - Wenri Zhang; Jian Cheng; Kamila Vagnerova; Yulia Ivashkova; Jennifer Young; Anda Cornea; Marjorie R. Grafe; Stephanie J. Murphy; Patricia D. Hurn; Ansgar M. Brambrink (Translational Stroke Research, 2014)

Influence of Unloading Rate on the Strainburst Characteristics of Beishan Granite Under True-Triaxial Unloading Conditions - X. G. Zhao; J. Wang; M. Cai; C. Cheng; L. K. Ma; R. Su; F. Zhao; D. J. Li (Rock Mechanics and Rock Engineering, 2014)

The role of cold shock domain proteins in inflammatory diseases - Jonathan A. Lindquist; Sabine Brandt; Anja Bernhardt; Cheng Zhu; Peter R. Mertens (Journal of Molecular Medicine, 2014)

Both GLS silencing and GLS2 overexpression synergize with oxidative stress against proliferation of glioma cells - Mercedes Martín-Rufián; Renata Nascimento-Gomes; Ana Higuero; Amanda R. Crisma; José A. Campos-Sandoval; María C. Gómez-García; Carolina Cardona; Tzuling Cheng; Carolina Lobo; Juan A. Segura; Francisco J. Alonso; Monika Szeliga; et al. (Journal of Molecular Medicine, 2014)

Peginterferon plus Chinese herbal therapy is associated with a higher virological response than only peginterferon therapy in chronic hepatitis C - D. Cheng; E. Liu; Y. Li; R. Liu; L. Bai; Y. Chen; Y. Wang; Y. Chu; M. Wu; G. Cheng; S. Zhao (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Hydroxymethylation as a Novel Environmental Biosensor - T. Dao; R. Y. S. Cheng; M. P. Revelo; W. Mitzner; W. Y. Tang (Current Environmental Health Reports, 2014)

Trends in the susceptibility of methicillin-resistant Staphylococcus aureus to nine antimicrobial agents, including ceftobiprole, nemonoxacin, and tyrothricin: results from the Tigecycline In Vitro Surveillance in Taiwan (TIST) study, 2006–2010 - Y.-H. Chen; C.-Y. Liu; W.-C. Ko; C.-H. Liao; P.-L. Lu; C.-H. Huang; C.-T. Lu; Y.-C. Chuang; S.-M. Tsao; Y.-S. Chen; Y.-C. Liu; W.-Y. Chen; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Potential role of winter rainfall in explaining increased moisture in the Mediterranean and Middle East during periods of maximum orbitally-forced insolation seasonality - J. E. Kutzbach; G. Chen; H. Cheng; R. L. Edwards; Z. Liu (Climate Dynamics, 2014)

No evidence of interaction between known lipid-associated genetic variants and smoking in the multi-ethnic PAGE population - Logan Dumitrescu; Cara L. Carty; Nora Franceschini; Lucia A. Hindorff; Shelley A. Cole; Petra Bůžková; Fredrick R. Schumacher; Charles B. Eaton; Robert J. Goodloe; David J. Duggan; Jeff Haessler; Barbara Cochran; et al. (Human Genetics, 2013)

The association between pro-inflammatory cytokines, regional cerebral metabolism, and cognitive complaints following adjuvant chemotherapy for breast cancer - K. L. Pomykala; P. A. Ganz; J. E. Bower; L. Kwan; S. A. Castellon; S. Mallam; I. Cheng; R. Ahn; E. C. Breen; M. R. Irwin; D. H. S. Silverman (Brain Imaging and Behavior, 2013)

The California Breast Cancer Survivorship Consortium (CBCSC): prognostic factors associated with racial/ethnic differences in breast cancer survival - Anna H. Wu; Scarlett Lin Gomez; Cheryl Vigen; Marilyn L. Kwan; Theresa H. M. Keegan; Yani Lu; Salma Shariff-Marco; Kristine R. Monroe; Allison W. Kurian; Iona Cheng; Bette J. Caan; Valerie S. Lee; et al. (Cancer Causes & Control, 2013)

Automated Algorithm for GI Spike Burst Detection and Demonstration of Efficacy in Ischemic Small Intestine - Jonathan C. Erickson; Raisa Velasco-Castedo; Chibuike Obioha; Leo K Cheng; Timothy R. Angeli; Greg O’Grady (Annals of Biomedical Engineering, 2013)

Soil health as a predictor of lettuce productivity and quality: A case study of urban vacant lots - A. Knight; Z. Cheng; S. S. Grewal; K. R. Islam; M. D. Kleinhenz; P. S. Grewal (Urban Ecosystems, 2013)

Pupal diapause development and termination is driven by low temperature chilling in Bactrocera minax - Yong-Cheng Dong; Zhi-Jian Wang; Anthony R. Clarke; Rui Pereira; Nicolas Desneux; Chang-Ying Niu (Journal of Pest Science, 2013)

Population structure of Fusarium oxysporum f. sp. radicis-lycopersici in Florida inferred from vegetative compatibility groups and microsatellites - Cheng-Hua Huang; Pamela D. Roberts; Liane R. Gale; Wade H. Elmer; Lawrence E. Datnoff (European Journal of Plant Pathology, 2013)

Investigating the Role of Protein UnkG from the Pseudomonas putida UW4 in the Ability of the Bacterium to Facilitate Plant Growth - Wei Jiang; Zhenyu Cheng; Brendan J. McConkey; Bernard R. Glick (Current Microbiology, 2013)

Recent emergence of the wheat Lr34 multi-pathogen resistance: insights from haplotype analysis in wheat, rice, sorghum and Aegilops tauschii - Simon G. Krattinger; David R. Jordan; Emma S. Mace; Chitra Raghavan; Ming-Cheng Luo; Beat Keller; Evans S. Lagudah (Theoretical and Applied Genetics, 2013)

Wheat Zapper: a flexible online tool for colinearity studies in grass genomes - Loai M. Alnemer; Raed I. Seetan; Filippo M. Bassi; Charith Chitraranjan; Adam Helsene; Paul Loree; Steve Bou Goshn; Yong Q. Gu; Ming-Cheng Luo; M. Javed Iqbal; Gerard R. Lazo; Anne M. Denton; et al. (Functional & Integrative Genomics, 2013)

Sustained Analgesia Achieved Through Esterase-Activated Morphine Prodrugs Complexed with PAMAM Dendrimer - Brent B. Ward; Baohua Huang; Ankur Desai; Xue-Min Cheng; Mark Vartanian; Hong Zong; Xiangyang Shi; Thommey P. Thomas; Alina E. Kotlyar; Abraham Van Der Spek; Pascale R. Leroueil; James R. Baker (Pharmaceutical Research, 2013)

Potential hazards and dynamical analysis of interfacial solitary wave interactions - J. R.-C. Hsu; M. H. Cheng; Chen-Yuan Chen (Natural Hazards, 2013)

Rapid identification of novel functional promoters for gene therapy - Ian A. Pringle; Deborah R. Gill; Mary M. Connolly; Anna E. Lawton; Anne-Marie Hewitt; Graciela Nunez-Alonso; Seng H. Cheng; Ronald K. Scheule; Lee A. Davies; Stephen C. Hyde (Journal of Molecular Medicine, 2012)

Role of Neurotrophins in the Development and Function of Neural Circuits That Regulate Energy Homeostasis - Samira Fargali; Masato Sadahiro; Cheng Jiang; Amy L. Frick; Tricia Indall; Valeria Cogliani; Jelle Welagen; Wei-Jye Lin; Stephen R. Salton (Journal of Molecular Neuroscience, 2012)

Erratum to: Omega-6 docosapentaenoic acid-derived resolvins and 17-hydroxydocosahexaenoic acid modulate macrophage function and alleviate experimental colitis - Cheng-Ying Chiu; Beate Gomolka; Cordula Dierkes; Nora R. Huang; Maik Schroeder; Martin Purschke; Dieter Manstein; Bindi Dangi; Karsten H. Weylandt (Inflammation Research, 2012)

Bacteremia caused by Acinetobacter junii at a medical center in Taiwan, 2000–2010 - H.-Y. Tsai; A. Cheng; C.-Y. Liu; Y.-T. Huang; Y.-C. Lee; C.-H. Liao; P.-R. Hsueh (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Omega-6 docosapentaenoic acid-derived resolvins and 17-hydroxydocosahexaenoic acid modulate macrophage function and alleviate experimental colitis - Cheng-Ying Chiu; Beate Gomolka; Cordula Dierkes; Nora R. Huang; Maik Schroeder; Martin Purschke; Dieter Manstein; Bindi Dangi; Karsten H. Weylandt (Inflammation Research, 2012)

The Global Paleomonsoon as seen through speleothem records from Asia and the Americas - Hai Cheng; Ashish Sinha; Xianfeng Wang; Francisco W. Cruz; R. Lawrence Edwards (Climate Dynamics, 2012)

QTLs for murine red blood cell parameters in LG/J and SM/J F2 and advanced intercross lines - Thomas B. Bartnikas; Clarissa C. Parker; Riyan Cheng; Dean R. Campagna; Jackie E. Lim; Abraham A. Palmer; Mark D. Fleming (Mammalian Genome, 2012)

Molecular diversity of bacteria in Yunnan yellow cattle (Bos taurs) from Nujiang region, China - J. Leng; Y. M. Cheng; C. Y. Zhang; R. J. Zhu; S. L. Yang; X. Gou; W. D. Deng; H. M. Mao (Molecular Biology Reports, 2012)

Preliminary evidence of delayed spawning and suppressed larval growth and condition of the major carps in the Yangtze River below the Three Gorges Dam - Guo Zhang; Lang Wu; Hongtao Li; Ming Liu; Fei Cheng; Brian R. Murphy; Songguang Xie (Environmental Biology of Fishes, 2012)

Increasing trend of primary NO2 exhaust emission fraction in Hong Kong - Linwei Tian; Sarah R. Hossain; Hualiang Lin; Kin Fai Ho; Shun Cheng Lee; Ignatius T. S. Yu (Environmental Geochemistry and Health, 2011)

Stress-induced reinstatement of alcohol-seeking in rats is selectively suppressed by the neurokinin 1 (NK1) antagonist L822429 - Jesse R. Schank; Charles L. Pickens; Kelly E. Rowe; Kejun Cheng; Annika Thorsell; Kenner C. Rice; Yavin Shaham; Markus Heilig (Psychopharmacology, 2011)

A Random Comparative Study of Terbinafine Versus Griseofulvin in Patients with Tinea Capitis in Western China - S. Deng; H. Hu; P. Abliz; Z. Wan; A. Wang; W. Cheng; R. Li (Mycopathologia, 2011)

Floral display influences male and female reproductive success of the deceptive orchid Phaius delavayi - P. Li; B. Q. Huang; R. W. Pemberton; Y. B. Luo; J. Cheng (Plant Systematics and Evolution, 2011)

Impacts of hatchery release on genetic structure of rock carp Procypris rabaudi in the upper Yangtze River, China - Fei Cheng; Qingjiang Wu; Ming Liu; K. V. Radhakrishnan; Brian R. Murphy; Songguang Xie (Fisheries Science, 2011)

Comparison of a high-density genetic linkage map to genome features in the model grass Brachypodium distachyon - Naxin Huo; David F. Garvin; Frank M. You; Stephanie McMahon; Ming-Cheng Luo; Yong Q. Gu; Gerard R. Lazo; John Philip Vogel (Theoretical and Applied Genetics, 2011)

Laboratory experiments on waveform inversion of an internal solitary wave over a slope-shelf - Ming-Hung Cheng; John R.-C. Hsu; Chen-Yuan Chen (Environmental Fluid Mechanics, 2011)

EHPC 2010: sharing knowledge on environmental health for risk mitigation - T. E. Ford; A. L. Bass; S. Cheng; G. N. Cherr; B. Cole; E. Fairbairn; J.-D. Gu; R. S. Halbrook; F. E. Löffler; E. L. Madsen; N. A. McGinn (Ecotoxicology, 2011)

Expression of GDF-9, BMP-15 and their receptors in mammalian ovary follicles - R. Z. Sun; L. Lei; L. Cheng; Z. F. Jin; S. J. Zu; Z. Y. Shan; Z. D. Wang; J. X. Zhang; Z. H. Liu (Journal of Molecular Histology, 2010)

A Tandem Duplication of Manganese Superoxide Dismutase in Nosema bombycis and Its Evolutionary Origins - Heng Xiang; Guoqing Pan; Charles R. Vossbrinck; Ruizhi Zhang; Jinshan Xu; Tian Li; Zeyang Zhou; Cheng Lu; Zhonghuai Xiang (Journal of Molecular Evolution, 2010)

A multi-modeling approach to evaluating climate and land use change impacts in a Great Lakes River Basin - M. J. Wiley; D. W. Hyndman; B. C. Pijanowski; A. D. Kendall; C. Riseng; E. S. Rutherford; S. T. Cheng; M. L. Carlson; J. A. Tyler; R. J. Stevenson; P. J. Steen; P. L. Richards; et al. (Hydrobiologia, 2010)

Savicalin, a lipocalin from hemocytes of the soft tick, Ornithodoros savignyi - Paul H. Cheng; Ben J. Mans; Albert W. H. Neitz; Anabella R. M. Gaspar (Experimental and Applied Acarology, 2010)

Retro-transposon based genetic similarity within the genus Citrus and its relatives - Manosh Kumar Biswas; M. N. R. Baig; Yun-Jiang Cheng; Xiu-Xin Deng (Genetic Resources and Crop Evolution, 2010)

Roles of cysteines Cys115 and Cys201 in the assembly and thermostability of grouper betanodavirus particles - Chun-Hsiung Wang; Chi-Hsin Hsu; Yi-Min Wu; Yu-Chun Luo; Mei-Hui Tu; Wei-hau Chang; R. Holland Cheng; Chan-Shing Lin (Virus Genes, 2010)

Precise dating of abrupt shifts in the Asian Monsoon during the last deglaciation based on stalagmite data from Yamen Cave, Guizhou Province, China - Yan Yang; DaoXian Yuan; Hai Cheng; MeiLiang Zhang; JiaMing Qin; YuShi Lin; XiaoYan Zhu; R. Lawrence Edwards (Science China Earth Sciences, 2010)

Probing Cell Structure Responses Through a Shear and Stretching Mechanical Stimulation Technique - Robert L. Steward; Chao-Min Cheng; Danny L. Wang; Philip R. LeDuc (Cell Biochemistry and Biophysics, 2010)

Effects of sea states on seafloor compliance studies - Jui-Hsien Wang; Wu-Cheng Chi; R. Nigel Edwards; Eleanor C. Willoughby (Marine Geophysical Research, 2010)

Endosymbiotic copepods may feed on zooxanthellae from their coral host, Pocillopora damicornis - Y.-R. Cheng; C.-F. Dai (Coral Reefs, 2010)

Antimicrobial stewardship program directed at broad-spectrum intravenous antibiotics prescription in a tertiary hospital - V. C. C. Cheng; K. K. W. To; I. W. S. Li; B. S. F. Tang; J. F. W. Chan; S. Kwan; R. Mak; J. Tai; P. Ching; P. L. Ho; W. H. Seto (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

The infection process of the reef coral Stylophora pistillata by the parasitic copepod, Xarifia obesa - Y.-R. Cheng; C.-F. Dai (Coral Reefs, 2009)

Planning of municipal solid waste management systems under dual uncertainties: a hybrid interval stochastic programming approach - G. H. Cheng; G. H. Huang; Y. P. Li; M. F. Cao; Y. R. Fan (Stochastic Environmental Research and Risk Assessment, 2009)

Hypergravity results in human platelet hyperactivity - S. Li; Q. Shi; Z. Wang; R. Yan; H. Cheng; K. Dai (Journal of Physiology and Biochemistry, 2009)

Modelling the propagation of an internal solitary wave across double ridges and a shelf-slope - Ming-Hung Cheng; John R.-C. Hsu; Chen-Yuan Chen; Cheng-Wu Chen (Environmental Fluid Mechanics, 2009)

Structural characterization of Brachypodium genome and its syntenic relationship with rice and wheat - Naxin Huo; John P. Vogel; Gerard R. Lazo; Frank M. You; Yaqin Ma; Stephanie McMahon; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Plant Molecular Biology, 2009)

Replication kinetics of Salmonella enteritidis in internal organs of ducklings after oral challenge: a quantitative time-course study using real-time PCR - S. X. Deng; A. C. Cheng; M. S. Wang; X. R. Li; B. Yan (Veterinary Research Communications, 2009)

Nicotine is a Selective Pharmacological Chaperone of Acetylcholine Receptor Number and Stoichiometry. Implications for Drug Discovery - Henry A. Lester; Cheng Xiao; Rahul Srinivasan; Cagdas D. Son; Julie Miwa; Rigo Pantoja; Matthew R. Banghart; Dennis A. Dougherty; Alison M. Goate; Jen C. Wang (The AAPS Journal, 2009)

Ligand-induced nuclear translocation of S1P1 receptors mediates Cyr61 and CTGF transcription in endothelial cells - Rosendo Estrada; Lichun Wang; Venkatakrishna R. Jala; Jen-Fu Lee; Cheng-Yon Lin; Robert D. Gray; Bodduluri Haribabu; Menq-Jer Lee (Histochemistry and Cell Biology, 2009)

Investigation of the Drug–Drug Interaction Between α-Lipoic Acid and Valproate via Mitochondrial β-oxidation - Lee Cheng Phua; Lee Sun New; Catherine W. Goh; Aveline H. Neo; Edward R. Browne; Eric C. Y. Chan (Pharmaceutical Research, 2008)

Carbon assimilation, 𝛅 13 C and water relations of Elaeagnus angustifolia grown at two groundwater depths in the Minqin desert, China - Z. Shi; R. Cheng; S. Liu; G. Sorrentino; M. Centritto (Plant Biosystems, 2008)

Ly49h is necessary for genetic resistance to murine cytomegalovirus - Tammy P. Cheng; Anthony R. French; Beatrice F. M. Plougastel; Jeanette T. Pingel; Michael M. Orihuela; Mark L. Buller; Wayne M. Yokoyama (Immunogenetics, 2008)

Differential Responses of Wheat Inhibitor-like Genes to Hessian Fly, Mayetiola destructor, Attacks During Compatible and Incompatible Interactions - Junxiang Wu; Xuming Liu; Shize Zhang; Yu-Cheng Zhu; R. Jeffrey Whitworth; Ming-Shun Chen (Journal of Chemical Ecology, 2008)

Experiments on mixing and dissipation in internal solitary waves over two triangular obstacles - Chen-Yuan Chen; John R.-C. Hsu; Ming-Hung Cheng; Cheng-Wu Chen (Environmental Fluid Mechanics, 2008)

The nuclear genome of Brachypodium distachyon: analysis of BAC end sequences - Naxin Huo; Gerard R. Lazo; John P. Vogel; Frank M. You; Yaqin Ma; Daniel M. Hayden; Devin Coleman-Derr; Theresa A. Hill; Jan Dvorak; Olin D. Anderson; Ming-Cheng Luo; Yong Q. Gu (Functional & Integrative Genomics, 2008)

Alternative splicing of the FGF antisense gene: differential subcellular localization in human tissues and esophageal adenocarcinoma - Shuo Cheng Zhang; Christie Barclay; Leigh Ann Alexander; Laurette Geldenhuys; Geoffrey A. Porter; Alan G. Casson; Paul R. Murphy (Journal of Molecular Medicine, 2007)

Promotion of plant growth by ACC deaminase-producing soil bacteria - Bernard R. Glick; Zhenyu Cheng; Jennifer Czarny; Jin Duan (European Journal of Plant Pathology, 2007)

Climate simulations for 1880–2003 with GISS modelE - J. Hansen; M. Sato; R. Ruedy; P. Kharecha; A. Lacis; R. Miller; L. Nazarenko; K. Lo; G. A. Schmidt; G. Russell; I. Aleinov; S. Bauer; et al. (Climate Dynamics, 2007)

Investigation of rice transgene flow in compass sectors by using male sterile line as a pollen detector - Q. H. Yuan; L. Shi; F. Wang; B. Cao; Q. Qian; X. M. Lei; Y. L. Liao; W. G. Liu; L. Cheng; S. R. Jia (Theoretical and Applied Genetics, 2007)

Urinary levels of RANTES and M-CSF are predictors of lupus nephritis flare - S. Tian; J. Li; L. Wang; T. Liu; H. Liu; G. Cheng; D. Liu; Y. Deng; R. Gou; Y. Wan; J. Jia; C. Chen (Inflammation Research, 2007)

Application of LIDAR Technique and MM5-CMAQ Modeling Approach for the Assessment of Winter PM10 Air Pollution: A Case Study in Beijing, China - D. S. Chen; S. Y. Cheng; J. B. Li; T. Chen; X. Y. Zhao; X. R. Guo; H. L. Hu; T. Yu (Water, Air, & Soil Pollution, 2007)

Real-time fluorogenic PCR assays for the detection of entA, the gene encoding staphylococcal enterotoxin A - Jennifer R. Horsmon; Cheng J. Cao; Akbar S. Khan; Mark V. Gostomski; James J. Valdes; Kevin P. O’Connell (Biotechnology Letters, 2007)

The two giant sister species of the Southern Ocean, Dissostichus eleginoides and Dissostichus mawsoni, differ in karyotype and chromosomal pattern of ribosomal RNA genes - L. Ghigliotti; F. Mazzei; C. Ozouf-Costaz; C. Bonillo; R. Williams; C.-H. C. Cheng; E. Pisano (Polar Biology, 2007)

Effect of triterpene acids of Eriobotrya japonica (Thunb.) Lindl. leaf on inflammatory cytokine and mediator induction from alveolar macrophages of chronic bronchitic rats - Y. Huang; J. Li; R. Wang; Q. Wu; Y. -H. Li; S. -C. Yu; W. -M. Cheng; Y. -Y. Wang (Inflammation Research, 2007)

Antimicrobial potentials of endophytic fungi residing in Quercus variabilis and brefeldin A obtained from Cladosporium sp. - F. W. Wang; R. H. Jiao; A. B. Cheng; S. H. Tan; Y. C. Song (World Journal of Microbiology and Biotechnology, 2007)

Two new chemical constituents from Daphne odora Thunb. var. marginata - W. Zhang; W. D. Zhang; R. H. Liu; Y. H. Shen; C. Zhang; H. S. Cheng; P. Fu; L. Shan (Natural Product Research, 2006)

Analysis of candidate genes on chromosome 2 in oral cleft case-parent trios from three populations - T. H. Beaty; J. B. Hetmanski; M. D. Fallin; J. W. Park; J. W. Sull; I. McIntosh; K. Y. Liang; C. A. VanderKolk; R. J. Redett; S. A. Boyadjiev; E. W. Jabs; S. S. Chong; et al. (Human Genetics, 2006)

Variations in Indoor PM10 Concentrations in Sixteen Homes in Guiyang City, People's Republic of China - Y. L. Cheng; M. Yan; J. L. Li; Z. R. Liu; Y. H. Bai; W. Tian; D. G. Wu; Q. Cheng (Bulletin of Environmental Contamination and Toxicology, 2006)

Real-time Fluorogenic PCR Assays for the Detection of entA, the Gene Encoding Staphylococcal Enterotoxin A - Jennifer R. Horsmon; Cheng J. Cao; Akbar S. Khan; Mark V. Gostomski; James J. Valdes; Kevin P. O'Connell (Biotechnology Letters, 2006)

Estimating the uncertainty in annual net ecosystem carbon exchange: spatial variation in turbulent fluxes and sampling errors in eddy‐covariance measurements - RAM OREN; CHENG‐I HSIEH; PAUL STOY; JOHN ALBERTSON; HEATHER R MCCARTHY; PETER HARRELL; GABRIEL G KATUL (Global Change Biology, 2006)
Above forest canopies, eddy covariance (EC) measurements of mass (CO 2 , H 2 O vapor) and energy exchange, assumed to represent ecosystem fluxes, are commonly made at one point in the roughness sublayer (RSL). A spatial variability experiment, in which EC measurements were made from six towers within the RSL in a uniform pine plantation, quantified large and dynamic spatial variation in fluxes. The spatial coefficient of variation (CV) of the scalar fluxes decreased with increasing integration time, stabilizing at a minimum that was independent of further lengthening the averaging period (hereafter a ‘stable minimum’). For all three fluxes, the stable minimum (CV=9–11%) was reached at averaging times ( τ p ) of 6–7 h during daytime, but higher stable minima (CV=46–158%) were reached at longer τ p (>12 h) during nighttime. To the extent that decreasing CV of EC fluxes reflects reduction in micrometeorological sampling errors, half of the observed variability at τ p =30 min is attributed to sampling errors. The remaining half (indicated by the stable minimum CV) is attributed to underlying variability in ecosystem structural properties, as determined by leaf area index, and perhaps associated ecosystem activity attributes. We further assessed the spatial variability estimates in the context of uncertainty in annual net ecosystem exchange (NEE). First, we adjusted annual NEE values obtained at our long‐term observation tower to account for the difference between this tower and the mean of all towers from this experiment; this increased NEE by up to 55 g C m −2 yr −1 . Second, we combined uncertainty from gap filling and instrument error with uncertainty because of spatial variability, producing an estimate of variability in annual NEE ranging from 79 to 127 g C m −2 yr −1 . This analysis demonstrated that even in such a uniform pine plantation, in some years spatial variability can contribute ∼50% of the uncertainty in annual NEE estimates.

Variability and inheritance of flowering time and duration in Actinidia chinensis (kiwifruit) - C. H. Cheng; A. G. Seal; S. J. Murphy; R. G. Lowe (Euphytica, 2006)

Single-Column Model Intercomparison for a Stably Stratified Atmospheric Boundary Layer - J. Cuxart; A. A. M. Holtslag; R. J. Beare; E. Bazile; A. Beljaars; A. Cheng; L. Conangla; M. Ek; F. Freedman; R. Hamdi; A. Kerstein; H. Kitagawa; et al. (Boundary-Layer Meteorology, 2006)

Tissue-Specific Expression and Drought Responsiveness of Cell-Wall Invertase Genes of Rice at Flowering - X. M. Ji; M. Raveendran; R. Oane; A. Ismail; R. Lafitte; R. Bruskiewich; S. H. Cheng; J. Bennett (Plant Molecular Biology, 2005)

GGM02 – An improved Earth gravity field model from GRACE - B. Tapley; J. Ries; S. Bettadpur; D. Chambers; M. Cheng; F. Condi; B. Gunter; Z. Kang; P. Nagel; R. Pastor; T. Pekker; S. Poole; et al. (Journal of Geodesy, 2005)

Endonuclease-like activity of heme proteins - Willy B. Tan; Wunhuey Cheng; Andrew Webber; Akhilesh Bhambhani; Michael R. Duff; Challa V. Kumar; George L. McLendon (JBIC Journal of Biological Inorganic Chemistry, 2005)

Axillary bud proliferation and organogenesis of Euphorbia pulchurrima winter rose - K. A. Pickens; Z. M. Cheng; R. N. Trigiano (In Vitro Cellular & Developmental Biology - Plant, 2005)

Comparative genetic maps reveal extreme crossover localization in the Aegilops speltoides chromosomes - Ming-Cheng Luo; Karin R. Deal; Zu-Li Yang; Jan Dvorak (Theoretical and Applied Genetics, 2005)

Genetic Analysis of Egyptian Date (Phoenix dactylifera L.) Accessions Using AFLP Markers - Ashraf M. El-Assar; Robert R. Krueger; Pachanoor S. Devanand; Chih-Cheng T. Chao (Genetic Resources and Crop Evolution, 2005)

Rapid construction of a patient-specific torso model from 3D ultrasound for non-invasive imaging of cardiac electrophysiology - L. K. Cheng; G. B. Sands; R. L. French; S. J. Withy; S. P. Wong; M. E. Legget; W. M. Smith; A. J. Pullan (Medical & Biological Engineering & Computing, 2005)

Comparison of catches on two types of collector of recently settled stages of the spiny lobster ( Panulirus argus ) , Florida, United States - B. F. Phillips; Y. W. Cheng; C. Cox; J. Hunt; N. K. Jue; R. Melville‐Smith (New Zealand Journal of Marine and Freshwater Research, 2005)
This study compared catches of Panulirus argus pueruli and very young juveniles between Hunt and Sandwich collectors at Long and Big Munson Keys, Florida, United States. Catch comparisons were made over the peak puerulus settlement period between February and July 2002, using six Sandwich and six Hunt collectors at each site. The collectors were set out in arrays and the relative positions of the two collector types were reversed each month after they had been checked and the catch removed. A total of 3470 pueruli and juveniles were collected; 2011 and 1459 by Sandwich and Hunt collectors, respectively. Sandwich collectors caught an average of 5.43 more pueruli and juveniles per check than Hunt collectors, with this difference being significant for catches of clear pueruli (P1s), pigmented pueruli (P3s), and juvenile stages (J1s and J2s) ( P 0.05), but not for catches of semi‐pigmented pueruli (P2s). The catches made by both collector types were highly dependant on the month of collection and site of the collectors ( P 0.01). Catches were generally not influenced by the location of the collector in the array ( P = 0.50), but corner collectors caught significantly fewer P1s, P2s, P3s, and J1s and J2s than all other collectors ( P 0.01). Conditioning time influenced the total catch ( P 0.01) but was not significant for all individual P1s, P2s, P3s, and J1s and J2s stages of development. Overall, the time taken for collectors to condition in Florida was less than the Sandwich collectors used for P. cygnus in Western Australia.

Use of convalescent plasma therapy in SARS patients in Hong Kong - Y. Cheng; R. Wong; Y. O. Y. Soo; W. S. Wong; C. K. Lee; M. H. L. Ng; P. Chan; K. C. Wong; C. B. Leung; G. Cheng (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Quaternary ecological and geomorphic changes associated with rainfall events in presently semi‐arid northeastern Brazil - Augusto S. Auler; Xianfeng Wang; R. Lawrence Edwards; Hai Cheng; Patrícia S. Cristalli; Peter L. Smart; David A. Richards (Journal of Quaternary Science, 2004)
Several geomorphic features and palaeobiotic remains in now semi‐arid northeastern Brazil indicate major palaeoenvironmental changes during past periods of increased rainfall. 230 Th mass spectrometric ages of speleothems and travertines have allowed the determination of the timing and duration of wetter than present conditions. The data demonstrate that wet events have occurred throughout much of the Pleistocene, present dry conditions having been established at the end of the Younger Dryas. A markedly different fauna comprising megafaunal elements not adapted to the present low arboreal scrubland caatinga vegetation existed in the area. Palaeobotanical remains embedded in travertine indicate forested vegetation at these wetter intervals, suggesting that the caatinga was then replaced or mixed with a semi‐deciduous forest. Due to the abundance of travertine sites containing fossil botanical remains in northeastern Brazil, it is believed that forest expansion occurred over large areas of the now semi‐arid zone, showing that the long hypothesised forested links between biodiversity‐rich Amazon and Atlantic rainforests may indeed have existed during these moister phases. Copyright © 2004 John Wiley & Sons, Ltd.

DNA extraction from archival formalin-fixed, paraffin-embedded tissues: heat-induced retrieval in alkaline solution - Shan-Rong Shi; Ram Datar; Cheng Liu; Lin Wu; Zina Zhang; Richard J. Cote; Clive R. Taylor (Histochemistry and Cell Biology, 2004)

Nitrogen Leaching and Denitrification in Continuous Corn as Related to Residue Management and Nitrogen Fertilization - Hero T. Gollany; Jean-Alex E. Molina; C. Edward Clapp; Raymond R. Allmaras; Milegua F. Layese; John M. Baker; H. H. Cheng (Environmental Management, 2004)

Multi-decadal thermohaline variability in an ocean–atmosphere general circulation model - W. Cheng; R. Bleck; C. Rooth (Climate Dynamics, 2004)

Mating Behavior of Cephalonomia tarsalis (Ashmead) (Hymenoptera: Bethylidae) and the Effect of Female Mating Frequency on Offspring Production - Ling-lan Cheng; Ralph W. Howard; James F. Campbell; Ralph E. Charlton; James R. Nechols; Sonny B. Ramaswamy (Journal of Insect Behavior, 2004)

CNS somatosensory-auditory interactions elicit or modulate tinnitus - R. A. Levine; M. Abel; H. Cheng (Experimental Brain Research, 2003)

Structural Determinants of P-Glycoprotein-Mediated Transport of Glucocorticoids - Charles R. Yates; Cheng Chang; Jeffrey D. Kearbey; Kazuto Yasuda; Erin G. Schuetz; Duane D. Miller; James T. Dalton; Peter W. Swaan (Pharmaceutical Research, 2003)

Mechanisms of Na + -K + -ATPase phosphorylation by PKC in the medullary thick ascending limb of Henle in the rat - Claudia A. Bertuccio; Sam X. Cheng; Elvira E. Arrizurieta; Rodolfo S. Martn; Fernando R. Ibarra (Pflügers Archiv - European Journal of Physiology, 2003)

Alterations in aortic antioxidant components in an experimental model of atherosclerosis: A time-course study - David V. Godin; Cathleen R. Nichols; Kenneth A. Hoekstra; Maureen E. Garnett; Kimberly M. Cheng (Molecular and Cellular Biochemistry, 2003)

Behavioral Interaction Between Males of Cephalonomia tarsalis (Ashmead) (Hymenoptera: Bethylidae) Competing for Females - Ling-lan Cheng; Ralph W. Howard; James F. Campbell; Ralph E. Charlton; James R. Nechols; Sonny Ramaswamy (Journal of Insect Behavior, 2003)

Dissecting the pet18mutation in Saccharomyces cervisiae: HTL1encodes a 7-kDa polypeptide that interacts with components of the RSC complex - Y.-M. Lu; Y.-R. Lin; A. Tsai; Y.-S. Hsao; C.-c. Li; M. Y. Cheng (Molecular Genetics and Genomics, 2003)

Peripartum Tuberculosis as a Form of Immunorestitution Disease - V. C. C. Cheng; P. C. Y. Woo; S. K. P. Lau; C. H. Y. Cheung; R. W. H. Yung; L. Y. C. Yam; K. Y. Yuen (European Journal of Clinical Microbiology & Infectious Diseases, 2003)

Anti-tumor immunoglobulin M increases lung metastasis in an experimental model of malignant melanoma - Nu-man Tsai; Bing-Mae Chen; Shao-Lun Wei; Cheng-Wen Wu; Steve R. Roffler (Clinical & Experimental Metastasis, 2003)

Surprisingly minor influence of TRAV11 (Vα14) polymorphism on NK T-receptor mCD1/α-galactosylceramide binding kinetics - Bee-Cheng Sim; Kaisa Holmberg; Stephane Sidobre; Olga Naidenko; Nathalie Niederberger; Shane D. Marine; Mitchell Kronenberg; Nicholas R. J. Gascoigne (Immunogenetics, 2003)

Characterization and Temporal Variation of Asian Dust Aerosol from a Site in the Northern Chinese Deserts - X. Y. Zhang; S. L. Gong; R. Arimoto; Z. X. Shen; F. M. Mei; D. Wang; Y. Cheng (Journal of Atmospheric Chemistry, 2003)

Brevetoxin Concentrations in Marine Aerosol: Human Exposure Levels During a Karenia brevis Harmful Algal Bloom - R. H. Pierce; M. S. Henry; P. C. Blum; J. Lyons; Y. S. Cheng; D. Yazzie; Y. Zhou (Bulletin of Environmental Contamination and Toxicology, 2003)

Differential genome duplication and fish diversity - Rongjia Zhou; Hanhua Cheng; Terrence R. Tiersch (Reviews in Fish Biology and Fisheries, 2002)

Lactococcus garvieae , a cause of disease in grey mullet, Mugil cephalus L., in Taiwan - S‐C Chen; L‐L Liaw; H‐Y Su; S‐C Ko; C‐Y Wu; H‐C Chaung; Y‐H Tsai; K‐L Yang; Y‐C Chen; T‐H Chen; G‐R Lin; S‐Y Cheng; et al. (Journal of Fish Diseases, 2002)

Downregulation of PTEN/MMAC/TEP1 expression in human prostate cancer cell line DU145 by growth stimuli - Dhundy R. Bastola; Gurcharan S. Pahwa; Ming-Fong Lin; Pi-Wan Cheng (Molecular and Cellular Biochemistry, 2002)

Differential distribution of interneurons in the neural networks that control walking in the mudpuppy (Necturus maculatus) spinal cord - J. Cheng; K. Jovanovic; Y. Aoyagi; D. J. Bennett; Y. Han; R. B. Stein (Experimental Brain Research, 2002)

Inheritance and expression of the cry1Ab gene in Bt (Bacillus thuringiensis) transgenic rice - G. Wu; H. Cui; G. Ye; Y. Xia; R. Sardana; X. Cheng; Y. Li; I. Altosaar; Q. Shu (Theoretical and Applied Genetics, 2002)

Expression of afibrobacter succinogenes 1,3-1,4-β-glucanase in Potato (Solanum tuberosum) - John D. Armstrong; G. Douglas Inglis; Lawrence M. Kawchuk; Tim A. McAllister; Fran Leggett; Dermot R. Lynch; L. Brent Selinger; K. J. Cheng (American Journal of Potato Research, 2002)

Establishment of a gene transfer system for Pseudozyma flocculosa, an antagonistic fungus of powdery mildew fungi - Y. Cheng; F. Belzile; P. Tanguay; L. Bernier; R. Bélanger (Molecular Genetics and Genomics, 2001)

Physiologic Plasticity, Evolution, and Impacts of a Changing Climate on Pinus Contorta - Gerald E. Rehfeldt; William R. Wykoff; Cheng C. Ying (Climatic Change, 2001)

Segregation distortion at marker loci: variation during microspore embryogenesis in maize - P. Dufour; C. Johnsson; S. Antoine-Michard; R. Cheng; A. Murigneux; M. Beckert (Theoretical and Applied Genetics, 2001)

Cryopreservation of heart cells from the eastern oyster - Ta Chih Cheng; Jerome F. La Peyre; John T. Buchanan; Terrence R. Tiersch; Richard K. Cooper (In Vitro Cellular & Developmental Biology - Animal, 2001)

CRYOPRESERVATION OF HEART CELLS FROM THE EASTERN OYSTER - TA CHIH CHENG; JEROME F. LA PEYRE; JOHN T. BUCHANAN; TERRENCE R. TIERSCH; RICHARD K. COOPER (In Vitro Cellular & Developmental Biology - Animal, 2001)

Chromosome assignments of the rice field eel Sox9 and Sox17 genes - X. Huang; R. Zhou; L. Liu; H. Cheng; Y. Guo; Q. Yu (Aquaculture International, 2000)

Acute Toxicity of Inorganic Chloramines to Daphnia magna in Two Types of Dilution Water - M. T. Wan; R. G. Watts; W. Cheng (Bulletin of Environmental Contamination and Toxicology, 2000)

Acute Toxicity of Inorganic Chloramines to Daphnia magna in Two Types of Dilution Water - M. T. Wan; R. G. Watts; W. Cheng (Bulletin of Environmental Contamination and Toxicology, 2000)

Field evaluation of a passive sampler for the exposure assessment of 2-methoxyethanol - T.-S. Shih; C.-Y. Chen; R.-I. Cheng; L.-J. Wu (International Archives of Occupational and Environmental Health, 2000)

Acute Toxicity of Chlorine-Produced Oxidants (CPO) to the Marine Invertebrates Amphiporeia virginiana and Eohaustorius washingtonianus - M. T. Wan; G. Van Aggelen; W. Cheng; R. G. Watts (Bulletin of Environmental Contamination and Toxicology, 2000)

Abstracts of presentations on selected topics at the XIVth international plant protection congress (IPPC) July 25–30, 1999 - R. Hull; H. A. Kuiper; Maryvon Y. Noordam; Marjorie A. Hoy; Jenny S. Cory; A. C. Fereres; P. Gonzalez; F. Meins; Y. Elkind; Benedicte Charrier; P. Meyer; M. Metzlaff; et al. (Phytoparasitica, 1999)

Brodifacoum Poisoning of Avian Scavengers During Rat Control on a Seabird Colony - G. R. Howald; P. Mineau; J. E. Elliott; K. M. Cheng (Ecotoxicology, 1999)

Polyploidization in embryogenic microspore cultures ofBrassica napus L. cv. Topas enables the generation of doubled haploid clones by somatic embryogenesis - X. XuHan; H. -C. Jing; X. -F. Cheng; A. Iwanowska; H. Kieft; J. H. W. Bergervoet; S. P. C. Groot; R. J. Bino; A. A. M. van Lammeren (Protoplasma, 1999)

Immunolocalization of the petunia floral binding proteins 7 and 11 during seed development in wild-type and expression mutants ofPetunia hybrida - P. E. Wittich; R. F. de Heer; X. -F. Cheng; H. Kieft; L. Colombo; G. C. Angenent; A. A. M. van Lammeren (Protoplasma, 1999)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)

Altered expression of sialylated carbohydrate antigens in HT29 colonic carcinoma cells - David R. Mack; Pi-Wan Cheng; Fulvio Perini; Shu Wei; Michael A. Hollingsworth (Glycoconjugate Journal, 1998)

Method for mapping a partial lethal-factor locus on a molecular-marker linkage map of a backcross and doubled-haploid population - R. Cheng; A. Kleinhofs; Y. Ukai (Theoretical and Applied Genetics, 1998)

Molecular characterization of the creatine kinases: and some historical perspectives - Wenning Qin; Zaza Khuchua; Judy Cheng; Jaime Boero; R. Mark Payne; Arnold W. Strauss (Molecular and Cellular Biochemistry, 1998)

SKF 38393 enhances odor detection performance - R. L. Doty; Cheng Li; Ritu Bagla; William Huang; Cheryl Pfeiffer; Gary M. Brosvic; Judith M. Risser (Psychopharmacology, 1998)

Usefulness of the carbon-13 tracer technique for characterizing terrestrial carbon pools - R. Liu; C.E. Clapp; H.H. Cheng (Nutrient Cycling in Agroecosystems, 1997)

Expression and inheritance of foreign genes in transgenic peanut plants generated by Agrobacterium-mediated transformation - M. Cheng; R. L. Jarret; Z. Li; J. W. Demski (Plant Cell Reports, 1997)

Expression and inheritance of foreign genes in transgenic peanut plants generated byAgrobacterium-mediated transformation - M. Cheng; Z. Li; J. W. Demski; R. L. Jarret (Plant Cell Reports, 1997)

Tenidap inhibits 5-lipoxygenase product formation in vitro, but this activity is not observed in three animal models - T. J. Carty; F. J. Sweeney; R. J. Griffiths; J. D. Eskra; M. J. Ernest; J. S. Pillar; J. D. Cheng; L. D. Loose; P. A. Joseph; P. P. Pazoles; P. F. Moore; A. Nagahisa; et al. (Inflammation Research, 1997)

Production and cytogenetics of Brassica campestris-alboglabra chromosome addition lines - B. Y. Chen; B. F. Cheng; R. B. Jørgensen; W. K. Heneen (Theoretical and Applied Genetics, 1997)

Cloning and expression of an amylase gene from Streptococcus bovis in Escherichia coli - Rhonda G. Clark; Y. -J. Hu; Michael F. Hynes; R. Keith Salmon; K. -J. Cheng (Archives of Microbiology, 1992)

Co-expression of hepatitis B virus antigens by a non-defective adenovirus vaccine vector - Wei Wei Ye; B. B. Mason; Murty Chengalvala; Sheau-Mei Cheng; G. Zandle; M. D. Lubeck; Shaw-Guang Lee; Satoshi Mizutani; A. R. Davis; P. P. Hung (Archives of Virology, 1991)

Factors affecting consumers’ choices among types of potatoes: A multinomial logit analysis - Hsiang-tai Cheng; Alan S. Kezis; Stephanie R. Peavey; Duane A. Smith (American Journal of Potato Research, 1991)

Factors affecting consumer purchase decision for round white potatoes - H. Cheng; A. S. Kezis; S. R. Peavey; D. A. Smith (American Journal of Potato Research, 1990)

Carbamate insecticide removal in laundering from cotton and polyester fabrics - Jaw Hua Chiao-Cheng; Barbara M. Reagan; Randall R. Bresee; Clifton E. Meloan; Ahmed M. Kadoum (Archives of Environmental Contamination and Toxicology, 1988)

Comparison of the primate alphaherpesviruses - Siao-Wen Mou; J. K. Hilliard; Cheng-Hui Song; R. Eberle (Archives of Virology, 1986)